Prevalence of Klebsiella pneumoniae in raw milk and biocontrol potential of phage vB_Kpn_18-1 - Ting Qin; Xinyan Yao; Dai Peng; Chaoxiang Jia; Linlin Huang; Yingqian Han; Yanbin Yang; Yang Liu; Guoyu Yang; Juan Geng; Yueying Wang; Heping Li (International Dairy Journal, 2026)

Recycling sludge carbon sources via different iron-based activated PDS into denitrification systems for nitrogen removal: focusing on efficacy, community structure and molecular mechanism - Zhiying Lv; Hong You; Haoran Leng; Hao Sheng; Weirun Li; Feng Liu; Zhipeng Li; Jing Zhu; Guoyu Zhang (Bioresource Technology, 2026)

Human impacts on fish biodiversity in the Yangtze River Basin: a multidimensional assessment using the Cumulative Change in Biodiversity Facets (CCBF) index - Juan Du; Kangshun Zhao; Sébastien Brosse; Guoyu He; Jun Xu; Lixiong Yu; Daqing Chen; Mingdian Liu; Xinbin Duan; Guohuan Su (Reviews in Fish Biology and Fisheries, 2026)

3D chromatin architecture-related genes orchestrate LUAD evolution and therapy resistance: insights from integrative machine learning and spatial single-cell mapping - Yahao Jing; Yuying Xing; Yangyang Liu; Ningxuan Zhang; Yudan Pan; Wenhao Zhang; Chenglin Zhu; Zhenyue Zhong; Guoyu Zhang; Ji-Cheng Li; Xiaotao Dong (Functional & Integrative Genomics, 2026)

Petrogenesis of ∼1.96 Ga Mafic–Intermediate Intrusions in the Daqingshan Area: Constraints on the Tectonic Evolution of the Khondalite Belt, North China Craton - Yundi Gong; Xiaojie Dong; Zhongyuan Xu; Guanghui Lian; Zhenghong Liu; Guoyu Fan (Journal of Asian Earth Sciences, 2026)

Nanotherapy to enhance melanoma immunotherapy through DHA-assisted modulation and disruption of iron/calcium ion homeostasis - Zehao Liu; Chuanmeng Zhang; Lianlian Zhang; Jingyuan Cao; Ji Yu; Qingqing Zhang; Wenxiang Gao; Guoyu Wang; Gongye Di; Yuhan Li; Tianyi Liu; Ming Yin; et al. (Chemical Engineering Journal, 2026)

Leucine zipper-inspired Fmoc-programmed peptide nanoassemblies for membrane damage-driven postoperative cancer immunotherapy and infection control - Guoyu Xia; Jingwen Sun; Liyuan Peng; Weiyu Xing; Lulu Wang; Zhen Zheng (Chemical Engineering Journal, 2026)

The coarse-grained active layer as a thermal shield: Mechanisms of ice-debris complexes preservation at a retreating glacier margin in the Tianshan Mountains, China - Yu Zhou; Wenhai Shi; Guoyu Li; Wei Ma; Qingsong Du; Dun Chen; Junhao Chen (Cold Regions Science and Technology, 2026)

Adsorption mitigated aggregation controls sedimentation of sulfonamide antibiotics in complex with dissolved black carbon - Jie Liang; Guoyu Li; Jingyi Zhang; Ning Tang; Lan Lu; Qing Cai; Wenjia Kong; Genying Zeng; Xingzhong Yuan (Water Research, 2026)

Monitoring-constrained GPR inversion reveals profile-scale hydrothermal heterogeneity in a retrogressive thaw slump - Shunshun Qi; Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Fujun Niu; Mingtang Chai; Yougang Yang; Qingsong Du; Kai Gao; Yapeng Cao; Jiawei Yang (Journal of Hydrology, 2026)

Distribution, risk assessment and transport mechanisms of heavy metals in typical regions of the Tibetan Plateau - Jingrui Han; Yanmei Zhou; Mengfan Nie; Guanzhe Yao; Zhisen Guo; Jin Wang; Guoyu Ding (Journal of Environmental Chemical Engineering, 2026)

Isolation and characterization of broad-host-range bacteriophages and their alleviation of liver and kidney injury in a mouse model of S. aureus infection - Xinyan Yao; Linlin Huang; Chaoxiang Jia; Dai Peng; Rui Cao; Xiangshun Sun; Yingqian Han; Yang Liu; Yanbin Yang; Guoyu Yang; Yueying Wang; Heping Li (Food Research International, 2026)

ZnO/Ni3ZnC0.7 with Znδ+-Niδ- interface synergistically promoting CO2 activation and hydrogen spillover for highly selective CO2 hydrogenation to CO - Sihe Peng; Yuetong Wang; Guoyu Yue; Haoyu Qi; Chao Zhang (Chemical Engineering Journal, 2026)

The potential role of the Sox9a protein in regulating cyp19a transcription and ovarian development in the olive flounder (Paralichthys olivaceus) - Chang Shu; Lijuan Wang; Congcong Zou; Xungang Tan; Yuxia Zou; Zhihao Wu; Yan Liu; Qiaowan Wu; Ling Wang; Guoyu Wang; Ze Li; Feng You (Theriogenology, 2026)

Organizing heritage-tree landscape-perception and CES representations in a historic district: A node–time–touchpoint approach - Fengshang Chen; Qingjun He; Wei Wang; Guoyu Wang; Yuqing Feng (Journal of Environmental Management, 2026)

Zearalenone-induced hepatotoxicity: Underlying mechanisms and genistein-mediated preventive effects - Ruo Du; Qingyuan Li; Yi Cheng; Yuting Zeng; Mairewulan Abula; Wenyi Liu; Fangfang Yu; Weihua Jia; Yuhui Du; Yue Ba; Yanjie Wang; Guoyu Zhou (Food and Chemical Toxicology, 2026)

Performance and microbial community dynamics of an internal circulating photogranular membrane bioreactor for synthetic mariculture wastewater treatment under different hydraulic retention times - Weirun Li; Guoyu Zhang; Lingjie Li; Yiwen Ding; Hong You; Yi Ding; Jing Zhu; Zhipeng Li (Environmental Research, 2026)

Weekly thermal-hydrologic activation windows of retrogressive thaw slumps: Implications for early warning of slope instability in degrading permafrost regions - Shunshun Qi; Guoyu Li; Wei Ma; Dun Chen; Fujun Niu; Mingtang Chai; Yougang Yang; Jiawei Yang; Fei Wang; Qingsong Du; Yapeng Cao; Xiaoran Duan (Engineering Geology, 2026)

Stabilization mechanisms and contributions of mineral-associated microbial necromass to soil organic carbon in coastal wetlands - Jine Wei; Biao Zhu; Changwei Lü; Fenfen Zhang; Yanling Zheng; Xiaofei Li; Hongpo Dong; Xia Liang; Guoyu Yin; Min Liu; Lijun Hou (CATENA, 2026)

Computationally assisted combinatorial rational design of xylanase with improved thermostability and catalytic performance for lignocellulosic biomass hydrolysis - Yan Zou; Guoyu Liu; Xueying Zeng; Jia Liu; Haotian Wang; Jingtao Zhang; Hairong Hu; Guankai Hao; Jie Liu; Shenglin Duan; Peng Yuan; Xiuting Li (Bioresource Technology, 2026)

Water level reduction and fish stock management promote restoration of submerged plants in shallow lakes, while enhancing phytoplankton diversity and stability - Xinlian Zheng; Guoyu Xu; Erik Jeppesen; Xianfei Huang; Guojun Cai; Jie Liu; Xue Peng; Pinhua Xia (Water Research, 2026)

Multiscale evolution of mechanical and fractal behaviors of coal gasification coarse slag improved loess under cyclic freezing-thawing: experimental observation and microstructural interpretation - Jiawei Yang; Libo Wu; Guoyu Li; Zhanju Lin; Rulong Yao (Transportation Geotechnics, 2026)

Projected response of global rainfall-induced landslides to future climate change - Kailiang Zhao; Haijun Qiu; Ya Liu; Guoqing Yang; Zijing Liu; Wanqi Luo; Yaru Zhu; Guoyu Wang; Mohib Ullah (Journal of Hydrology, 2026)

Corrigendum to “Fluoride-induced male reproductive toxicity: Dual-tissue pyroptosis in the gut-testis axis mediated by inflammatory cytokines”, J. Hazard. Mater. (2026) 142537 - Shu Niu; Yuhui Du; Bin Liu; Zichen Feng; Guoqing Wang; Chunxiang Li; Yan Wang; Qing Sun; Fangfang Yu; Guoyu Zhou; Yue Ba (Journal of Hazardous Materials, 2026)

Fluoride-induced male reproductive toxicity: Dual-tissue pyroptosis in the gut-testis axis mediated by inflammatory cytokines - Shu Niu; Yuhui Du; Bin Liu; Zichen Feng; Guoqing Wang; Chunxiang Li; Yan Wang; Qing Sun; Fangfang Yu; Guoyu Zhou; Yue Ba (Journal of Hazardous Materials, 2026)

Decoupling of soil reactive oxidized and reduced nitrogen gas emissions across a coastal wetland reclamation chronosequence - Wentao Qiao; Lingling Deng; Ruhai Wang; Zehua Fu; Guoyu Yin; Dianming Wu (Journal of Environmental Management, 2026)

MiR-8159-x and miR-200-z induced liver injury of tsinling lenok trout through endoplasmic reticulum and mitochondria interaction under high-temperature stress - Fang Ma; Lei Shen; Dunting Tie; Minlan Yang; Yang Lin; Guoyu Song (Fish Physiology and Biochemistry, 2026)

Spatiotemporal Variation of Tropospheric Temperature Lapse Rate Over the Chinese Mainland and Its Potential Influencing Factors - Yun Qin; Guoyu Ren; Yongqiang Zhang; Panfeng Zhang; Yunjian Zhan; Kangmin Wen (International Journal of Climatology, 2026)
Using daily data from 123 radiosonde stations in China, we characterise the spatiotemporal variation of tropospheric temperature lapse rate (TLR) during 1961–2024 and analyse its potential influencing factors. Over the Chinese mainland, the multi‐year annual mean TLR is 6.4°C/km, increasing from southeast to northwest, with maxima in spring (6.8°C/km) and minima in winter (6.1°C/km). Distinct regional patterns emerge: steep TLRs occur over the eastern Tibetan Plateau in cold seasons (> 7.2°C/km), while shallow winter TLRs are observed in the southern Yangtze River basin (

Biocontrol potential of entomopathogenic nematodes against the soil-dwelling larvae of Colaspoides femoralis Lefèvre (Coleoptera: Eumolpidae) - Feng Hu; Guoyu Zhao; Mingjie Liang; Rongmeng Lan; Qiang Bao; D.M.S.M. Dassanayaka; W.H. Jayasinghe; Linhong Jin (Crop Protection, 2026)

Systematic analysis of photogranulation characteristics during start-up of a photogranular sequencing batch bioreactor for mariculture wastewater treatment - Weirun Li; Zhipeng Li; Guoyu Zhang; Lingjie Li; Yixuan Yang; Shuyu Zhao; Hong You; Yi Ding; Jing Zhu (Marine Pollution Bulletin, 2026)

Bioinformatics and experimental insights into the relationship between ferroptosis and fluoride-induced neurotoxicity - Qinyang Qin; Yuhui Du; Xinying Wang; Leizhen Duan; Yi Cheng; Weihua Jia; Wenyi Liu; Xi Yan; Fangfang Yu; Yue Ba; Guoyu Zhou (NeuroToxicology, 2026)

Facile low-temperature synthesis of a bacillus subtilis-inspired ionic liquid demulsifier with multiple hydrophilic heads - Baiyun Jin; Fan Ye; Wei Zhou; Guoyu Xiang; Zhoucheng Li; Yu Ding; Wentao Ma; Yuanzhu Mi (Journal of Hazardous Materials, 2026)

Long-term embankment deformation of the Qinghai-Tibet Highway in permafrost regions - Zhizhong Sun; Wei Ma; Guoyu Li; Yongzhi Liu; Guilong Wu; Fan Yu; Shujuan Zhang (Cold Regions Science and Technology, 2026)

Multi-domain characterization of propeller cavitation noise using spectral-coherence-weighted synchronous modulation spectrum for quantifying rotation-synchronous modulation - Beini Wen; Huiyun Hao; Ming Hong; Qin Wu; Biao Huang; Guoyu Wang (Ocean Engineering, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Utilization of waste sludge-derived biochar in sustainable planting ecological concrete: Integrating structural, ecological, and environmental benefits - Fanrun Huang; Wei Xiong; Guoyu Jiang; Xinyan Xiong; Hongqiang Chu; Huajie Huang; Hainan Wu; Chi Zhang (Environmental Research, 2026)

Tower foundation-induced through talik characteristics in warm permafrost terrains: The case of power lines in Jagdaqi, Northeast China - Juncen Lin; Guoyu Li; Kai Gao; Fei Wang; Hang Zhang (Engineering Geology, 2026)

Solvent-induced structural transformation and dynamic luminescence modulation in hybrid Sb-based chlorides for multi-level encryption - Liqing Wang; Xingjun Li; Sizhe Liu; Wei Zhang; Xiaoli Luo; Xiaobo Gu; Guoyu Tang; Yao Lin; Xiaoying Shang; Shan Lu; Xueyuan Chen (Chemical Engineering Journal, 2026)

Attributing improved diurnal temperature range simulations in CMIP6 to enhanced forcing responses - Xiubao Sun; Chunzai Wang; Wei Lin; Guoyu Ren; Xiaoying Xue; Siqi Zhang (Atmospheric Research, 2026)

Integrative metabolomic and transcriptomic analyses reveal coordinated variation in phenolic acid metabolism and redox-related traits in Ocimum basilicum accessions - Jingtian Yang; Zhengqiao Liao; Jialin Li; Mei Liu; Yanping Mao; Guoyu Yang; Lei Liu (Planta, 2026)

Coumarin metabolites in Ocimum: chemical diversity, biosynthetic pathways, and network pharmacology-based prediction of multi-target anticancer potential - Jingtian Yang; Jialin Li; Wuzhi Jiaba; Jing Yuan; Mei Liu; Lingliang Guan; Guoyu Yang (Plant Molecular Biology, 2026)

Collapse–subsidence retrogressive thaw slumps in degrading permafrost: multi-source insights from the Northeastern Qinghai–Tibet Plateau - Shunshun Qi; Dun Chen; Guoyu Li; Mingtang Chai; Yougang Yang; Qingsong Du; Yapeng Cao; Hang Zhang; Jintao Jiang; Anshuang Su; Miao Wang (Landslides, 2026)

Mutual information guided domain adaptation network for unsupervised transfer fault diagnosis of offshore wind turbines under time-varying conditions and scarce labels - Yun Kong; Guoyu Huang; Cuiying Lin; Haiqiang Wang; Qinkai Han; Junyu Qi; Hui Liu; Fulei Chu (Ocean Engineering, 2026)

Study on hull-propeller interaction of a catamaran during self-propulsion - Xinbo Wang; Guoyu Xu; Jianhao Zhang; Jichao Yang; Yuhao Cen; Changzi Wang; Xiaodong Liu; Shengli Wang (Ocean Engineering, 2026)

Purifying ⁶⁰Co-containing low-level radioactive wastewater via electro-deionization with zirconium phosphate ion-exchange resins - Jinzheng Yuan; Haodong Jiang; Jinghao Guo; Hanzhi Wang; Guoyu Wen; Manuel César Martí-Calatayud; Jueyin Gong; Yuanhang Wang; Li Lin; Feng Luo; Tao Luo; Xinlong Wang (Journal of Hazardous Materials, 2026)

Synergistic effects of alternate intercropping on crop productivity and soil carbon storage enhance systemic sustainability - Lei Yang; Wenjun Jin; Xiaofei Chen; Ruidong Sun; Weixia Lei; Jianhao Wei; Lingcong Kong; Dagang Wang; Zhiping Huang; Guoyu Hu; Xiangbei Du (European Journal of Agronomy, 2026)

miR-133a-3p promotes T-2 toxin-induced chondrocyte damage via targeting IGF1R - Kangting Luo; Lingyu Wang; Zhengyan Zhang; Yikai Hu; Chengyu Zhao; Shuiyuan Yu; Qian Li; Zaichao Dong; Tongtong Sha; Miao Wang; Juan Zuo; Yanjie Dou; et al. (Chemico-Biological Interactions, 2026)

Legume intercropping in tea plantations modulates soil microbiome for enhanced profitability: A mechanistic link to economic returns - Guangyun Cao; Xia Zhou; Guoyu Zhao; Jiayong Qin; Xiuju Yang; Qinghui Zeng; Linhong Jin (Applied Soil Ecology, 2026)

Semantic segmentation of deep-sea polymetallic nodules based on an improved DeepLabV3+ algorithm - Jichao Yang; Tongbo Xu; Jinghao Zhu; Wenquan Zhang; Qing Zhao; Guoyu Xu; GuanHong Zhai (Marine Georesources & Geotechnology, 2026)

Macro-meso mechanical response of ice-bearing glaciofluvial deposits under thaw–freeze–thaw cycles - Yifan Zhang; Liang Tang; Xiangxun Kong; Shuang Tian; Xianzhang Ling; Shanzhen Li; Guoyu Li (Transportation Geotechnics, 2026)

Visible-light-driven photocatalytic degradation of pharmaceutical residues using ternary (W, Ni, and Mn) single-atom anchored BiVO4-Co3O4/C3N5 nanocomposites - Yueshuai Wang; Karuppaiah Selvakumar; Muthuraj Arunpandian; Meenakshisundaram Swaminathan; P. Karuppusamy; N. Dinesh Kumar; Tae Hwan Oh; Guoyu Huang; Mohamed A. Habila; Ahmed Aljuwayid (Journal of Water Process Engineering, 2026)

Microwave-biochar synergistic carbon thermal reduction for the recovery of Fe and Cr from stainless steel dust: A waste upgrading strategy - Guoyu Cui; Xiang Zhang; Yanghui Xu; Guojun Ma; Dingli Zheng; Ju Xu; Xi Zhou (Journal of Environmental Chemical Engineering, 2026)

Anthropogenic warming of China and constrained future projection: updated investigation based on urbanization-bias adjusted observations and CMIP6 models - Jintao Zhang; Guoyu Ren; Qinglong You; Kangmin Wen (Climatic Change, 2026)

Stable cropping intensity and dominant human-induced productivity improvement in the trajectory of land use intensification in eastern China - Guoyu Li; Yu Cao; Samantha L. Lima; Hang Chen; Yangfei Huang; Bryan C. Pijanowski (Advances in Space Research, 2026)

Effects of Spartina alterniflora invasion on carbon, nitrogen, phosphorus and silicon stoichiometry in coastal saltmarsh wetlands - Jian Li; Zhanrui Leng; Guoyu Luo; Longyun Lai; Shan Jiang (Acta Oceanologica Sinica, 2026)

Corrigendum to “Assessment of pavement–subgrade deformation in permafrost highways using UAV photogrammetry and ground-penetrating radar: Case study of Qinghai–Tibet highway” [Transp. Geotech. 57 (2026) 101899] - Shunshun Qi; Guoyu Li; Jiawei Yang; Qingsong Du; Kai Gao; Dun Chen; Mingtang Chai; Anshuang Su; Miao Wang (Transportation Geotechnics, 2026)

Numerical assessment of erosion risk for composite hydrofoils by the potential energy theoretical method - Ruhan Shao; Rui Yuan; Housheng Zhang; Qin Wu; Biao Huang; Guoyu Wang (Ocean Engineering, 2026)

Microwave-assisted activation of hydrogen peroxide by zero-valent iron with different morphologies for crystal violet wastewater treatment: Performance, stability, and degradation mechanism - Jiapeng Zhang; Shumiao Hou; Jing Zhu; Qinghao Li; Wenye Li; Guoyu Zhang; Feng Liu; Hong You; Zhipeng Li (Journal of Environmental Sciences, 2026)

MOF-derived AgCl/ZnO heterojunction photocatalysts: Enhanced degradation of tetracycline via promoted charge carrier separation - Kailai Zhang; Ao Feng; Chuwen Ou; Qinwu Wu; Zhen Meng; Hang Chen; Shurui Xu; Xiaobo Fu; Wenbo Liao; Baizeng Fang; Guoyu Zhong (Environmental Research, 2026)

Enhancing 1O2 pathway via ultrasound-coupled iron-carbon activated persulfate for improving sludge dehydration and reducing antibiotics mutagenicity - Zhiying Lv; Feng Liu; Hong You; Haoran Leng; Weirun Li; Zhipeng Li; Jing Zhu; Guoyu Zhang (Environmental Research, 2026)

Interfacial environment modulation by nanoneedle-shaped polyaniline for enhanced hydrogen isotope separation by water electrolysis - Rui Li; Guoyu Li; Penghui Xiong; Yuhan Wu; Ruidong Liu; Hang Zhong; Yue Yao; Xin Xiang; Wenhua Luo; Jingsong Xu (Chemical Engineering Journal, 2026)

Thawing permafrost under Qinghai-Xizang Highway and its impacts on road performance based on multi-source observed data - Guoyu Li; Mingtang Chai; Wei Ma; Fujun Niu; Dun Chen; Qingsong Du; Yu Zhou; Shunshun Qi; Yapeng Cao; Jianbing Chen; Liyun Tang; Yan Zhang (Cold Regions Science and Technology, 2026)

mTOR pathway mediates the endoplasmic reticulum stress -apoptosis of CD4+ T cell through inhibiting autophagy flux in sepsis - Xianli Lei; Guoyu Zhao; Yawen Xie; Na Cui (Inflammation Research, 2026)
Background CD4 + T cells are major reactive subpopulation for cellular and humoral immune responses following sepsis. The apoptosis of CD4 + T cells may contribute to sepsis-induced immunosuppression, and preventing the induction of endoplasmic reticulum stress (ERS) can ameliorate apoptosis of CD4 + T cells in sepsis. The mechanistic target of rapamycin (mTOR) pathway performs an essential regulatory role on ERS-apoptosis of CD4 + T cells. This study aims to elucidate the underlying mechanisms of mTOR regulation of ERS-apoptosis of CD4 + T cells. Methods In this study, based on the cecal ligation and puncture (CLP) model, 4-phenylbutyric acid (4-PBA), we firstly detected the percentage of ERS-apoptosis of CD4 + T cells with flow cytometry, Western blotting. Next, we observed the autophagy process and related makers with transmission electron microscopy (TEM) and Western blotting. Furthermore, we created CLP models with T cell-specific mTOR and TSC1 genetic knockout mice, and bafilomycin A1(Baf-A1), a selective inhibitor of autophagy to explore the regulatory role and underlying mechanism of mTOR on ERS-apoptosis of CD4 + T cells. With rapamycin, we proved the clinical potential of mTOR. Results Here we observed a considerably higher percentage of apoptotic CD4 + T cells in sepsis, and 4-PBA (an inhibitor of ERS) could alleviate not only ERS, but also the apoptosis of CD4 + T cells. As our previous work proved, deletion of mTOR decreased ERS-apoptosis of CD4 + T cells in sepsis. Furthermore, deficient autophagy, especially impaired autophagic flux was observed in sepsis. Mechanistically, we found knockdown of mTOR erased impaired autophagic flux, decreased ER stress-induced apoptosis, which could be reversed by Baf-A1. More importantly, rapamycin (inhibitor of mTOR) showed great clinical potential. Conclusion we proved that mTOR deletion could alleviate CD4 + T cells ERS-apoptosis by rescuing autophagy involving autophagosome –lysosome fusion. For the first time, we demonstrate the mTOR-autophagy-ERS-apoptosis axis in sepsis, enriching the targets for future discovery of new sepsis therapies.

Spatial and historic changes of nutrients across the changjiang river and associated major tributaries - Qiuxun Lin; Zhenyang Song; Mengting Qi; Guoyu Yin; Dongyao Sun; Ye Li; Lijun Hou; Min Liu; Xiaofei Li (Water Research, 2026)

Assessment of pavement–subgrade deformation in permafrost highways using UAV photogrammetry and ground-penetrating radar: Case study of Qinghai–Tibet highway - Shunshun Qi; Guoyu Li; Jiawei Yang; Qingsong Du; Kai Gao; Dun Chen; Mingtang Chai; Anshuang Su; Miao Wang (Transportation Geotechnics, 2026)

High-efficiency lithium isotope separation via electrodeposition: Mechanistic insight and material design principles - Siyu Xiao; Leshan Yan; Changyan Lu; Nan Xiao; Yun Li; Siliang Liu; Yang Lu; Liangxing Jiang; Zongliang Zhang; Guoyu Qian; Fangyang Liu (Journal of Environmental Chemical Engineering, 2026)

Investigation of spray design and heat transfer evolution mechanisms in radiant syngas cooler - Guoyu Zhang; Yan Gong; Weidong Xia; Qinghua Guo; Lihong Yu; Guangsuo Yu (Fuel, 2026)

Flavonoid diversity across six Ocimum accessions: UPLC–MS/MS metabolomics and RNA-seq reveal anticancer leads and nutraceutical potential - Jingtian Yang; Jialin Li; Mengling Yu; Jing Yuan; Wuzhi Jiaba; Lijun Zhu; Qian Wang; Guoyu Yang (Food Research International, 2026)

Global distribution of suitable habitats for deep-sea sponges based on machine learning - Jichao Yang; Tongbo Xu; Xuelei Zhang; QinZeng Xu; Guoyu Xu; Guanhong Zhai; Minxing Dong (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Evaluation of resin regeneration and effluent recovery pathways for sustainable perchlorate removal from fireworks wastewater - Jingjing Li; Yanxia Yang; Guoyu Qiu; Qimeng Li; Wentao Li; Xinhou Zhang; Guoxiang Wang (Chemical Engineering Journal, 2026)

Ultrasonic enhanced Fe-C/PDS system for sludge dewatering and carbon source release: synergy of oxidation and cracking processes - Wenye Li; Binghan Xie; Zhipeng Li; Guoyu Zhang; Zhiying Lv; Qinghao Li; Shuyu Zhao; Mu Tong; Yuanyuan Gao; Langming Bai (Bioresource Technology, 2026)

Cooling Front Controls on Co Mineralization within Skarn-Type Co-Rich Fe Deposits: A Numerical Modeling Case Study of the Zhuchong Deposit, Anhui Province, China - Xunyu Hu; Xian Liang; Fangyue Wang; Ye Qiu; Guangxian Liu; Yue Li; Yi Chang; Jie Zhou; Guoyu Zhou (Natural Resources Research, 2026)

Neoarchaean granitoid complexes in the Laoling area, Jilin Province, North China Craton: transition from mantle plume to plate subduction - Guoyu Fan; Xiaojie Dong; Yusong Chen; Zhenghong Liu; Zhongyuan Xu (International Geology Review, 2026)

Multifunctional utilization in buildings using a Mn7Co3Ce1Ox heterojunction photo-thermal catalyst - Feiyang Xu; Qingsong Lu; Huabo Wu; Jing Li; Guoyu Zhang; Jie Ji; Bendong Yu (Energy and Buildings, 2026)

Constructing an asymmetric electronic microenvironment using PtRu bimetallic with different work functions to promote the synergistic photocatalytic dry reforming of methane - Guoyu Wang; Jianfeng Zheng; Zhiyu Zhang; Hongqiang Yang; Xinru Li; Yan Cui; Zhanggen Huang (Chemical Engineering Journal, 2026)

HIF-1α/BNIP3L–mediated mitophagy is involved in T-2 toxin–induced myocardial injury - Qian Li; Miao Wang; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Huanxia Zhang; Yanjie Dou; Guoyu Zhou; Yue Ba; Fang-fang Yu (Chemico-Biological Interactions, 2026)

Effect of freeze-thaw cycle on biochar-stabilized heavy metal contaminated soils: A comparative analysis in seasonally frozen regions with and without groundwater recharge - Jun Zhang; Zhijun Zhang; Jiangshan Li; Dahu Rui; Lianli Xu; Guoyu Li (Cold Regions Science and Technology, 2026)

Thawing warm permafrost of quicklime (CaO) piles and their optimization design - Yuncheng Mao; Shanzhi Fan; Guoyu Li; Dun Chen; Changqing Zhao; Yanhu Mu; Haihong Zhang; Chunqing Li; Xiaosen Li; Xiaolin Li (Cold Regions Science and Technology, 2026)

Long-term performance and optimization of two-phase closed thermosyphons for buried large-scale warm-oil pipelines under rising oil temperature - Wenyuan Lei; Yapeng Cao; Guoyu Li; Dong Li; Yujun Cui; Shaoqun Lin; Yan Zhang; Anshuang Su; Miao Wang; Xu Wang (Cold Regions Science and Technology, 2026)

Concurrent occurrence of droughts and floods between the upper Hanjiang river and Northern North China at multi-temporal scales: an association with Arctic Oscillation - Xiaodan Zhang; Guoyu Ren; Yuda Yang (Climate Dynamics, 2026)

Inhibition of LDHA promotes GSDME-dependent pyroptosis by activating RIG-I-like receptor signaling - Cuiqing Xie; Xiaojuan Xu; Senzhen Wang; Wei Li; Zhengwei Guo; Chaojie Wang; Lei Gao; Fujun Dai; Guoyu Zhang (Apoptosis, 2026)

Accelerated warming and salinification in China’s semi-enclosed shallow sea revealed by homogenized long-term observations - Yan Li; Guoyu Ren; Qingyuan Wang; Xue Han; Jianghua Lv; Xiaomei Liao (Acta Oceanologica Sinica, 2026)

Nitrogen transformation and N2O production pathways under arsenic and cadmium stress in Chongming Island, China - Yinghui Jiang; Guoyu Yin; Minghua Nie; Caixia Yan; Mingjun Ding; Hua Zhang; Mei Lei; Yong Ge (Marine Pollution Bulletin, 2025)

Biodiversity–carbon relationships in urban wilderness: Evidence for synergies, trade-offs, and low-intervention strategies - Shangchun Hu; Jing Que; Jiahui Liu; Yujia Li; Xing Su; Baoqin Li; Guoyu Wang (Journal of Environmental Management, 2025)

Identifying the sources and accumulation trends of heavy metals in representative polluted farmland on the Loess Plateau - Lirui Zhang; Tao Chen; Guoyu Wang; Ruiyun Jing; Xiaoli Zhu; Bing Kou; Shi Zhou; Songlin Zhang (CATENA, 2025)

Culvert damage assessment and probability modeling in permafrost regions: A case study of the Qinghai-Tibet highway - Shunshun Qi; Guoyu Li; Dun Chen; Qingsong Du; Anshuang Su; Xu Wang; Liyun Tang; Yan Zhang; Miao Wang (Cold Regions Science and Technology, 2025)

Aryl hydrocarbon receptor (AhR) alleviates the LPS-induced inflammatory responses in IPEC-J2 cells by activating PINK1/Parkin-mediated mitophagy - Mengfei Ma; Jianxun Guo; Xiaoying Su; Baocai Ma; Xiufen Wang; Mingyu Wangshao; Kai Zhong; Yueying Wang; Guoyu Yang; Yingqian Han (Inflammation Research, 2025)

Heterogeneity analysis and prognostic model construction of HPV negative oral squamous cell carcinoma T cells using ScRNA-seq and bulk-RNA analysis - Chunyan Li; Zengbo Lv; Chongxin Li; Shixuan Yang; Feineng Liu; Tengfei Zhang; Lin Wang; Wen Zhang; Ruoyu Deng; Guoyu Xu; Huan Luo; Yinhong Zhao; et al. (Functional & Integrative Genomics, 2025)

Temperature and rainfall mediate soil-plant microbiome assembly in tropical rubber plantations - Yaqing Wei; Xicai Zhang; Wentao Peng; Zhixiang Wu; Guoyu Lan (Applied Soil Ecology, 2025)

Performance activation and syngas evolution mechanism of Ca-based industrial waste carbide slag on catalytic gasification of Mongolian bituminous coal - Zhiqing Lian; Guoyu Mao; Yanpeng Ban; Keduan Zhi; Jianxiu Hao; Huacong Zhou; Na Li; Quansheng Liu (Fuel, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

Potential use of plasma-activated water cleaning for aflatoxin B1 degradation in peanuts - Ruonan Ma; Cui Xu; Junxia Feng; Hangbo Xu; Yongqin Fan; Guoyu Zhou; Ximei Dai; Dongjie Cui; Zhen Jiao (Food Chemistry, 2025)

Self-supported Ni5P4/CoP/Ni-Foam electrode for enhancing hydroxide ion adsorption in supercapacitor applications - Weiwei Wang; Hongliang Wang; Sencheng Cai; Enhui Jin; Xinyu Zhou; Guoyu Jia; Guancheng Xu; Li Zhang (Chemical Engineering Journal, 2025)

Permafrost degradation due to fire disturbance: A case study in the Da Xing’anling mountains, Northeastern China - Yapeng Cao; Guoyu Li; Wei Ma; Yujun Cui; Dun Chen; Kai Gao; Juncen Lin; Changqing Li; Anshuang Su (CATENA, 2025)

Properties of ground surface temperature within the Engineering Corridor traversing the Xing'an permafrost region in Northern Northeast China - Juncen Lin; Hang Zhang; Guoyu Li; Anshuang Su; Xu Wang; Miao Wang; Kai Gao; Dun Chen (Cold Regions Science and Technology, 2025)

Deformation mechanism and multilayer cooling strategy in a warm permafrost transition zone: The case study of a dry bridge along the Qinghai-Tibet Railway - Kun Chen; Guoyu Li; Qihao Yu; Yanhui You; Lei Guo; Zhenyu Zhang; Jinxin Lu (Cold Regions Science and Technology, 2025)

Assessing urban rewilding potential: Plant diversity and public landscape perceptions in urban wildscapes of Harbin, China - Shangchun Hu; Jiahui Liu; Jing Que; Yujia Li; Xing Su; Baoqin Li; Guoyu Wang (Urban Forestry & Urban Greening, 2025)

Characteristics of carbon, nitrogen, and phosphorus in soil aggregates under different restoration methods on cut slopes in the Qinghai-Tibet Plateau mining area - Ziye Xu; Shenghao Ai; Meihua Sheng; Zhuojun Li; Yifan Leng; Jinqiang Ma; Guoyu Zhu; Yingwei Ai (Journal of Environmental Management, 2025)

Bentonite supported cobalt catalyst prepared by blending method for the catalytic oxidation of desulfurization by-product sulfite: Catalytic performance and mechanism - Fanbo Zeng; Jing Zhu; Feng Liu; Guoyu Zhang; Weirun Li; Wenye Li; Zhiwei Shang; Hong You; Shuxiao Wang; Zhipeng Li (Journal of Environmental Sciences, 2025)

Assessment of agricultural heat resources based on urbanization-bias-corrected data: case of a county in Heilongjiang, China - LI CHEN; GUOYU REN; CHANGMING ZHOU; LEI WEI; YABIN LI; HONGYAN SHI; SONG WU (Theoretical and Applied Climatology, 2025)

Aridity simplified the bacterial network and thus reduced soil multifunctionality in arid and semiarid regions - Liguo Dong; Xiaoxiong Bai; Xuan Yu; Guoyu Zhang; Sile Hu; Chengjie Ren; Sheng Zhang (Plant and Soil, 2025)

First report of Fusarium fujikuroi causing leaf blight on Chinese yew - Yao Charles Meto; Guoyu Wei; Huayang Xu; Yuling Jiang; Hongfei Gao; Anlong Hu (Crop Protection, 2025)

Cold atmospheric plasma-derived ROS detoxifies deoxynivalenol-induced nephrotoxicity - Ruonan Ma; Junxia Feng; Hangbo Xu; Xiaoying Zhou; Chunli Liu; Guoyu Zhou; Dongjie Cui; Yupan Zhu; Junhu Wan; Dezheng Yang; Gautam Sethi; Xudong Yang; et al. (Journal of Hazardous Materials, 2025)

Achieving high ZTave in n-type PbS via overall carrier concentration optimization and anharmonicity engineering - Yiqing Wei; Junji Chen; Zizhen Zhou; Bin Zhang; Jie Liu; Guoyu Wang; Xu Lu; Peng Yu; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

Kinematic mechanisms of coordinated fore and hind hoof movements for stability enhancement and energy efficiency in reindeer long-distance migration - Kaixiang Chen; Rui Zhang; Wenchao Dong; Hao Pang; Guoyu Li; Lige Wen (Polar Biology, 2025)

The Impact of the COVID-19 Pandemic on Iodine Nutrition Status of Pregnant Women and Infants/Toddlers: Repeated Cross-Sectional Studies in Zhengzhou, China - Weihua Jia; Yuhui Du; Qinyang Qin; Weixia Lu; Ruili Lyu; Leizhen Duan; Fangfang Yu; Yuanqing Zhang; Yue Ba; Qiuming Wang; Guoyu Zhou (Biological Trace Element Research, 2025)

The effect of various anionic types of inorganic salts on the wettability of solutions of surfactants - Bingyou Jiang; Guoyu Gao; Xiao-Han Wang; Bo Ren; Shulei Shi; Jie Wang (Process Safety and Environmental Protection, 2025)

Association of prenatal exposure to ozone with childhood emotional and behavioral problems and the modification of polyunsaturated fatty acids: A birth cohort study - Xiaonan Gu; Mengfan Li; Qian Chen; Yu Liu; Shuyue Huang; Xuanqing He; Guoyu Zhang; Lizi Lin; Li Cai (International Journal of Hygiene and Environmental Health, 2025)

The effects of skew parameter on the water jet propulsion pump with special emphasis on transient performances - Yuhu Wang; Tairan Chen; Biao Huang; Yikai Li; Guoyu Wang (Ocean Engineering, 2025)

Increasing the light–dark ratio enhances nitrogen removal performance by altering the mechanism in photogranules - Xiaodi Xing; Jing Zhu; Zhipeng Li; Guoyu Zhang; Weirun Li; Haili Tan; Binghan Xie; Yixuan Yang; Shuyu Zhao; Yi Ding; Hong You (Bioresource Technology, 2025)

Optimizing the spatial layout of mining areas to help carbon neutrality: land use change driven by improved NSGA II algorithms - Guoyu Wang; Jinsheng Zhou (Environment, Development and Sustainability, 2025)

Visual immunosensor assay with double T line for on-site sensitive fipronil pesticide detection in water, soil and honeysuckle - Shuai Kou; Guoyu Qiu; Liqiang Liu; Aihong Wu; Zheng Zhang; Hua Kuang; Chuanlai Xu; Xiaoling Wu (Journal of Hazardous Materials, 2025)

Decoding the relationship between farmland transfer and crop diversity: Insights from China - Hang Chen; Fei Meng; Guoyu Li; Jiwang Guo; Wenying Xiong; Xinhui Li; Yucheng Zou (Journal of Environmental Management, 2025)

Boosting the bioconversion efficiency of electric energy into Spirulina platensis biomass through LED light bars arrangement manipulation - Guoyu Ma; Lu Yuan; Qiping Gao; Yu Chen; Zhongzhen Cai; Liang Zhang; Dongdong Xiao; Liuqing Wang; Shusong Wu; Yahui Sun (Journal of Environmental Chemical Engineering, 2025)

Mixing Rubber Plantations with Native Tree (Mytilaria laosensis) Enhances Soil Environmental Quality - Dongling Qi; Zhixiang Wu; Guoyu Lan; Chuan Yang; Shaobin Li; Yingying Zhang (Journal of Soil Science and Plant Nutrition, 2025)

Spatial patterns and drivers of elevation dependency of extreme temperature changes on the Tibetan Plateau - Ke Yang; Weizhe Chen; Guoyu Ren; Rui Zhang (Climate Dynamics, 2025)

Controlling Negative and Positive Power for Efficiency Enhancement and Muscle Strain Mitigation During Squatting with a Portable Knee Exoskeleton - Shuangyue Yu; Lu Liu; Sainan Zhang; Antonio Di Lallo; Junxi Zhu; Qifei Wu; Guoyu Zuo; Xianlian Zhou; Hao Su (Annals of Biomedical Engineering, 2025)

Synergistic adhesion enhancement of double-crosslinking chitosan hydrogel via catechol-Fe3+ coordination and Schiff base - Guoyu Zhao; Tingting Gu; Licheng Chen; Lei Wang; Yuri V. Petrov; Vladimir E. Baulin; Aslan Yu Tsivadze; Dechang Jia; Yu Zhou; Baoqiang Li (Carbohydrate Polymers, 2025)

Spirulina (Arthrospira) cultivation in photobioreactors: From biochemistry and physiology to scale up engineering - Guoyu Ma; Qiping Gao; Lu Yuan; Yu Chen; Zhongzhen Cai; Liang Zhang; Jun Hu; Yunjun Wang; Shusong Wu; Yahui Sun (Bioresource Technology, 2025)

Quercetin Simultaneously Treats Skeletal Fluorosis and Kashin-Beck Disease by Modulating HIF-1 and Ferroptosis Signaling Pathways - Bin Liu; Yan Wang; Jingyuan Zhu; Hui Huang; Ruiqin Chen; Fangfang Yu; Guoyu Zhou; Yue Ba (Biological Trace Element Research, 2025)

A coupled hydrological multimedia model used to simulate PFASs transport and fate in the river network of megacity Shanghai - Ye Li; Tianhao He; Jing Yang; Fangfang Ding; Xiaofei Li; Ye Huang; Guoyu Yin; Erkai He; Yan Li; Yuyi Wang; Yushan Li; Yuyan Liu; et al. (Journal of Hydrology, 2025)

Removal and recovery of perchlorate from fireworks production wastewater through ion exchange and biological reduction processes - Jie Ma; Waseem ur Rahman; Peijun Du; Qimeng Li; Fei He; Guoyu Qiu; Guoxiang Wang; Xiaoguang Xu; Donglin Li; Ming Li; Shuizhong Lin (Journal of Environmental Management, 2025)

Pilot-scale demonstration of perchlorate-contaminated fireworks wastewater treatment through a combined ion-exchange and bioregeneration approach - Guoyu Qiu; Changkai Wang; Peijun Du; Qimeng Li; Fei He; Jie Ma; Donglin Li; Ming Li; Shuizhong Lin (Journal of Environmental Chemical Engineering, 2025)

Degradation mechanism of octadecylamine and 4-dodecylmorpholine in Salk Lake Brine under UV light - Taotao Liu; Wenwen Nie; Wei Song; Tong Zhou; Haiying Tang; Xinghai Li; Xuefeng Yu; Guoyu Zhang; Ning Zhao; Changsong Wang (Journal of Environmental Chemical Engineering, 2025)

Unraveling the interaction of dissolved organic matter and microorganisms with internal phosphorus cycling in the floodplain lake ecosystem - Lan Lu; Ning Tang; Ziqian Zhu; Ronghan Wang; Xiang Gao; Min Yan; Tingting Hu; Han Ma; Guoyu Li; Weixiang Li; Jingyi Zhang; Xiaodong Li; et al. (Environmental Research, 2025)

Histone methylation reprogramming underpins gene expression dynamics in Phytophthora during host infection - Haidong Shu; Guoyu Yin; Meihui Wu; Yujie Fang; Yufeng Fang; Yuanchao Wang; Han Chen; Suomeng Dong (Science China Life Sciences, 2025)

Gushan virus: a newly discovered virus found in mosquitoes of Shandong, China - Long Yuan; Yongchao Yang; Wenbing Zhu; Shuo Feng; Xinbei Li; Jian Song; Yujing Zhu; Guoyu Niu (Virus Genes, 2025)

Inflammation May Mediate the Effects of Fluoride on Liver and Kidney Function of Adults: Cross-Sectional Studies in China - Minghao Geng; Yi Cheng; Leizhen Duan; Guangshen Dong; Shuo Yang; Xuecheng Jiao; Weihua Jia; Hui Huang; Ming Dou; Xiaoli Fu; Fangfang Yu; Yuhui Du; et al. (Biological Trace Element Research, 2025)

Investigation of flow patterns and drag reduction effects of a ventilated supercavity regulated by an extra annular hydrofoil - Chao Liu; Liang Hao; Yue Wu; Qin Wu; Biao Huang; Guoyu Wang (Ocean Engineering, 2025)

A study on the efficiency and microbial community of anaerobic/anaerobic/anoxic/oxic membrane bioreactor for treating saline alkali-surfactant-polymer flooding wastewater - Xinxin Zhang; Dong Wei; Qian Lu; Qiushi Zhao; Jun Ma; Guoyu Liu; Jia Ouyang; Erming Luo; Chunying Li; Li Wei (Journal of Water Process Engineering, 2025)

The role of GSK3β signaling mediated lysosomal biosynthesis dysregulation in fluoride-induced neurological impairment - Yi Cheng; Yuhui Du; Yue Hu; Xinying Wang; Qingyuan Li; Xi Yan; Ming Dou; Weihua Jia; Fangfang Yu; Yue Ba; Guoyu Zhou (Food and Chemical Toxicology, 2025)

An overview of observed changes in precipitation totals and extremes over global land, with a focus on Africa - Tewodros Addisu Yate; Guoyu Ren (Earth-Science Reviews, 2025)

Optimizing ecological security patterns in a megacity by enhancing urban-rural connectivity: Insights from Wuhan, China - Lei Zhang; Yuwen Wan; Yuanyang Sun; Guoyu He; Xiqiong Lei; Xiaojian Wei; Gui Jin (Applied Geography, 2025)

Tahyna virus: an emerging threat to public health - Wenbing Zhu; Lijun Shao; Shuo Feng; Ke Lu; Xiaoli Yu; Guoyu Niu (Archives of Virology, 2025)

Q-learning assisted multi-objective evolutionary optimization for low-carbon scheduling of open-pit mine trucks - Yao Huang; Yinan Guo; Guoyu Chen; Hong Wei; Xiaoxiao Zhao; Shengxiang Yang; Shirong Ge (Swarm and Evolutionary Computation, 2025)

Association between maternal serum zinc and birth weight is modified by neonatal SOD2 polymorphism and promoter methylation - Yuting Zeng; Yalong Wang; Yanan He; Qinyang Li; Ruiqin Chen; Cuiping Wu; Na Li; Xinya Cheng; Yuhui Du; Fangfang Yu; Yue Ba; Guoyu Zhou (Journal of Trace Elements in Medicine and Biology, 2025)

Climate Change Drives Changes in the Size and Composition of Fungal Communities Along the Soil–Seedling Continuum of Schima superba - Xian Wu; M. Derek MacKenzie; Jiarong Yang; Guoyu Lan; Yu Liu (Molecular Ecology, 2025)
Plant microbiomes have a major influence on forest structure and functions, as well as tree fitness and evolution. However, a comprehensive understanding of variations in fungi along the soil–plant continuum, particularly within tree seedlings, under global warming is lacking. Here, we investigated the dynamics of fungal communities across different compartments (including bulk soil and rhizosphere soil) and plant organs (including the endosphere of roots, stems and leaves) of Schima superba seedlings exposed to experimental warming and drought using AccuITS absolute quantitative sequencing. Our results revealed that warming and drought significantly reduced the number of specific fungal amplicon sequence variants (ASVs) in the bulk soil and rhizosphere soil, respectively. Variations in fungal communities were mainly explained by compartments and plant organs, with the composition of endophytic fungal communities within leaves (primarily attributed to species gain or loss) being most influenced by climate change. Moreover, warming significantly reduced the migration of Ascomycota, soil saprotrophs, wood saprotrophs and yeasts from the bulk soil to the rhizosphere soil but increased that of plant pathogens from the roots to the stems. Drought significantly decreased the absolute abundances of Chytridiomycota, Glomeromycota and Rozellomycota, as well as the migration of ectomycorrhizal fungi from the bulk soil to the rhizosphere soil but increased that of plant pathogens. Warming could indirectly reduce leaf area by increasing the diversity of leaf pathogens. These findings have potential implications for enhancing the resilience and functioning of natural forest ecosystems under climate change through the manipulation of plant microbiomes, as demonstrated in agroecosystems.

Comprehensive Analysis of Immune Characteristics of Fluorosis and Cuprotosis-Related Genes in Fluorosis Targeted Drugs - Ruijie Ba; Bin Liu; Zichen Feng; Guoqing Wang; Shu Niu; Yan Wang; Xuecheng Jiao; Cuiping Wu; Fangfang Yu; Guoyu Zhou; Yue Ba (Biological Trace Element Research, 2025)

SS-YOLO: A Lightweight Deep Learning Model Focused on Side-Scan Sonar Target Detection - Na Yang; Guoyu Li; Shengli Wang; Zhengrong Wei; Hu Ren; Xiaobo Zhang; Yanliang Pei (Journal of Marine Science and Engineering, 2025)
As seabed exploration activities increase, side-scan sonar (SSS) is being used more widely. However, distortion and noise during the acoustic pulse’s travel through water can blur target details and cause feature loss in images, making target recognition more challenging. In this paper, we improve the YOLO model in two aspects: lightweight design and accuracy enhancement. The lightweight design is essential for reducing computational complexity and resource consumption, allowing the model to be more efficient on edge devices with limited processing power and storage. Thus, meeting our need to deploy SSS target detection algorithms on unmanned surface vessel (USV) for real-time target detection. Firstly, we replace the original complex convolutional method in the C2f module with a combination of partial convolution (PConv) and pointwise convolution (PWConv), reducing redundant computations and memory access while maintaining high accuracy. In addition, we add an adaptive scale spatial fusion (ASSF) module using 3D convolution to combine feature maps of different sizes, maximizing the extraction of invariant features across various scales. Finally, we use an improved multi-head self-attention (MHSA) mechanism in the detection head, replacing the original complex convolution structure, to enhance the model’s ability to focus on important features with low computational load. To validate the detection performance of the model, we conducted experiments on the combined side-scan sonar dataset (SSSD). The results show that our proposed SS-YOLO model achieves average accuracies of 92.4% (mAP 0.5) and 64.7% (mAP 0.5:0.95), outperforming the original YOLOv8 model by 4.4% and 3%, respectively. In terms of model complexity, the improved SS-YOLO model has 2.55 M of parameters and 6.4 G of FLOPs, significantly lower than those of the original YOLOv8 model and similar detection models.

N6-methyladenosine RNA methylation regulates microplastics-induced cell senescence in the rainbow trout liver - Fang Ma; Zhe Liu; Jinqiang Quan; Yijun Yuan; Jianzhou Wang; Xiangjun Zhou; Jing Wang; Lei Shen; Dunting Tie; Minlan Yang; Yang Lin; Guoyu Song; et al. (Science of The Total Environment, 2025)

New insights into the application of non consumable electrode electroslag remelting refining: Enhanced removal of inclusions in Ti-Si alloy based the reduction of Ti-bearing blast furnace slag by SoG-Si scraps - Guoyu Qian; Hao Wang; Sheng Pang; Yiwei Sun; Jianwei Guo; Dong Wang; Jie Zhou; Zhilin Sheng; Zhi Wang (Journal of Cleaner Production, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

Characterization of cooked off-flavor volatile sulfur-containing compounds in green tea and their thermal inhibition via (−)-epigallocatechin gallate - Xin Yao; Yangyang Li; Jun Tang; Jieyao Yu; Yanyan Zhang; Xiaochun Wan; Guoyu Zhang; Xiaoting Zhai (Food Chemistry, 2025)

Adaptive constraint-guided surrogate enhanced evolutionary algorithm for horizontal well placement optimization in oil reservoir - Qinyang Dai; Liming Zhang; Peng Wang; Kai Zhang; Guodong Chen; Zhangxing Chen; Xiaoming Xue; Jian Wang; Chen Liu; Xia Yan; Piyang Liu; Dawei Wu; et al. (Computers & Geosciences, 2025)

The change and urbanization effect on extreme temperature trends in the Yangtze River Basin - Siqi Zhang; Yuyu Ren; Guoyu Ren; Suonam Kealdrup Tysa (Theoretical and Applied Climatology, 2025)

In arid regions, the different intercropping systems reduce interspecific competition to improve system productivity - Shuai Zhang; Tingting Liu; Wenwen Wei; Zhe Li; Guoyu Li; Lei Shen; Xiuyuan Wang; Yun Zhu; Luhua Li; Wei Zhang (Plant and Soil, 2025)

The variations of summer days and frost days in the Yangtze River Basin and their influencing factors - Siqi Zhang; Guoyu Ren; Xiubao Sun; Suonam Kealdrup Tysa; Panfeng Zhang; Yuyu Ren (Climate Dynamics, 2025)

Supplementation of Epimedium polysaccharide (EPS) improves goat semen characteristics following cryopreservation - Yu Li; Hui Wang; Zhangtao Hu; Guoyu Zhang; Fei Wen; Ming Xian; Songmao Guo; Guangzhi Zhang; Xing Zhang; Jianhong Hu (Animal Reproduction Science, 2025)

Molecular-phylogenetic analyses of Babesia and Theileria species from small mammals and their ticks in northern China suggest new reservoirs of bovine and equine piroplasms - Ente Li; Xuanchen Wu; Lijuan Tang; Meihua Yang; Sándor Hornok; Chunju Zhang; Yujiang Zhang; Guoyu Zhao; Yuanzhi Wang (Veterinary Parasitology, 2024)

Corrigendum to 'Co-application of fungal metabolites and nanoparticles control bacterial wilt disease by regulating rhizosphere soil microbial communities' - Guoxing Luo; Guoyu Luo (South African Journal of Botany, 2024)

Naringin alleviates fluoride-induced neurological impairment: A focus on the regulation of energy metabolism mediated by mitochondrial permeability transition pore - Yuhui Du; Guoqing Wang; Bin Liu; Meng Guo; Xi Yan; Ming Dou; Fangfang Yu; Yue Ba; Guoyu Zhou (Science of The Total Environment, 2024)

Phosphorus pool distributions and adsorption-desorption characteristics of soil aggregates in cut slopes of a permafrost zone in the Qinghai-Tibetan Plateau - Tingting Chen; Meihua Sheng; Jingyao Xiao; Shenghao Ai; Jianing Kou; Qinqing Yang; Yingwei Ai; Jinqiang Ma; Guoyu Zhu; Xiaoyan Ai (Science of The Total Environment, 2024)

Study on cooling efficiency and mechanism of lithium-ion battery thermal runaway inhibition by additives enhanced water mist based on boiling heat transfer theory - Xiangming Hu; Zhiyuan Yang; Yurui Deng; Ming Li; Qingsong Wang; Hongbin Wei; Xiaoxuan Wei; Guoyu Han (Process Safety and Environmental Protection, 2024)

Experimental investigation on the ventilated cavitating flow characteristics around an axisymmetric body with an unsteady ventilation - Liang Hao; Housheng Zhang; Qingfeng Yang; Taotao Liu; Biao Huang; Guoyu Wang (Ocean Engineering, 2024)

Mapping N2O production pathways in estuarine and coastal sediments through coupled 15N tracing and N2O isotopocules analysis - Cheng Chen; Tianyu Yin; Guoyu Yin; Xia Liang; Xiaofei Li; Lijun Hou; Min Liu (Journal of Hydrology, 2024)

A sustainable machining method with high efficiency, high quality and low wear - electric arc electrochemical composite machining - Shengsheng Zhang; Jianping Zhou; Yinan Zhao; Guoyu Hu; Fei Fu; Lizhong Wang; Yan Xu (Journal of Cleaner Production, 2024)

Contribution for lake phytoplankton community succession under multi-source artificial hydrological regulation - Bowen Sun; Na Li; Guoyu Wang; Xueping Gao; Xushen Zhou; Fanqing Kong (Journal of Environmental Management, 2024)

Mechanism of membrane fouling mitigation by microalgae biofilm formation for low C/N mariculture wastewater treatment: EPS characteristics, composition and interfacial interaction energy - Yanbo Liu; Jing Zhu; Weirun Li; Binghan Xie; Guoyu Zhang; Yi Ding; Feng Liu; Haili Tan; Yuhong Jia; Hong You; Zhipeng Li (Journal of Environmental Chemical Engineering, 2024)

Serum calcium improves the relationship between fluoride exposure and hypothalamic-pituitary-testicular axis hormones levels in males—a cross-sectional study on farmers in the lower reaches of the Yellow River - Guoqing Wang; Leizhen Duan; Yuhui Du; Xiaoli Fu; Bin Liu; Xuanyin Zhang; Fangfang Yu; Guoyu Zhou; Yue Ba (Environmental Pollution, 2024)

Thermal stability of PVDF-HFP based gel electrolyte for high performance and safe lithium metal batteries - Xiaoxuan Wei; Yurui Deng; Xiangming Hu; Zhiyuan Yang; Guoyu Han; Hengxu Xu; Zhijun Zhang (Chemical Engineering Journal, 2024)

Pavement damage characteristics in the permafrost regions based on UAV images and airborne LiDAR data - Kai Gao; Guoyu Li; Dun Chen; Anshuang Su; Yapeng Cao; Chunqing Li; Gang Wu; Qingsong Du; Juncen Lin; Xu Wang; Shuai Huang; Liyun Tang; et al. (Cold Regions Science and Technology, 2024)

Co-application of fungal metabolites and nanoparticles control bacterial wilt disease by regulating rhizosphere soil microbial communities - Guoxing Luo; Guoyu Luo (South African Journal of Botany, 2024)

Revealing the catalytic behavior of different types ZVI (powder Fe0, sponge Fe1, foam Fe2) in US/Fex/PDS and its effect on the dewaterability of waste activated sludge - Zhiying Lv; Hong You; Haoran Leng; Weirun Li; Shuangyue Yang; Zhipeng Li; Jing Zhu; Guoyu Zhang (Chemical Engineering Journal, 2024)

Improving broadband absorption of carbon dot conjugated melanin via pre-doping strategy as interfacial photothermal evaporator - Guoyu Kan; Yukong Li; Qing Chang; Xiaoyong Deng; Yijun Xie (Chemical Engineering Journal, 2024)

Rational composition engineering toward high thermoelectric performance in p-type EuMg2Sb2-based materials - Jian Yu; Hongpan Zhu; Zizhen Zhou; Xiaofang Liu; Guang Han; Bin Zhang; Xu Lu; Guoyu Wang; Xiaoyuan Zhou (Chemical Engineering Journal, 2024)

Accurately estimate soybean growth stages from UAV imagery by accounting for spatial heterogeneity and climate factors across multiple environments - Yingpu Che; Yongzhe Gu; Dong Bai; Delin Li; Jindong Li; Chaosen Zhao; Qiang Wang; Hongmei Qiu; Wen Huang; Chunyan Yang; Qingsong Zhao; Like Liu; et al. (Computers and Electronics in Agriculture, 2024)

Glutamine metabolism in fluorosis: Integrated metabolomics and transcriptomics analysis - Yue Ba; Shu Niu; Zichen Feng; Shuo Yang; Shuiyuan Yu; Chaofan Shi; Xuecheng Jiao; Guoyu Zhou; Fangfang Yu (Science of The Total Environment, 2024)

Land use and spatial contiguity are key driven factors of antibiotic multimedia patterns in the megacity river network - Fangfang Ding; Ye Li; Tianhao He; Yuyi Wang; Yushan Li; Ye Huang; Guoyu Yin; Jing Yang; Shixue Wu; Yuyan Liu; Min Liu (Science of The Total Environment, 2024)

Numerical simulation-based targeting of the Au mineralization within the Hongbu Altered Rock type gold deposit, Eastern Shandong Peninsula, China - Xunyu Hu; Ruyi Chen; Guangxian Liu; Kun Wang; Hui Yang; Yuhua Chen; Jie Zhou; Guoyu Zhou (Journal of Geochemical Exploration, 2024)

Novel dual-photoelectrode Z-scheme PEC system for efficient TBBPA removal and debromination: Performance and promoting mechanism - Haoran Leng; Wenqian Li; Zhiying Lv; Zhipeng Li; Guoyu Zhang; Yuhong Jia; Hong you (Journal of Cleaner Production, 2024)

Heterojunction photocatalyst MnO2-CsSnI3 for highly efficient formaldehyde oxidation at room temperature - Zihan Bao; Yueshuai Wang; Jingcong Hu; Jiguo Geng; Sai Ma; Hehe Liang; Guoyu Huang; Bohai Tian; Jianrui Feng; Yue Lu; Manling Sui (Chemical Engineering Journal, 2024)

Synthesis of two-dimensional petal-like LaCO3OH biochar for phosphorus capture from water at low concentrations - Qiaoling Xu; Jingjiang Xiao; Xuemei He; Guoyu Chen; Zhujian Huang; Tao Yuan; Lihua Cui; Haijiao Xie (Chemical Engineering Journal, 2024)

Sediment nitrate dissimilatory reduction processes in the river-lake ecotone of Poyang Lake, China: Mechanisms and environmental implications - Yinghui Jiang; Zhenglei Xie; Mingjun Ding; Hua Zhang; Gaoxiang Huang; Yun Cao; Guoyu Yin (Journal of Soils and Sediments, 2024)

Nitrogen input modulates the effects of coastal acidification on nitrification and associated N2O emission - Jie Zhou; Yanling Zheng; Lijun Hou; Lin Qi; Tieqiang Mao; Guoyu Yin; Min Liu (Water Research, 2024)

Long-term trends in human-induced water storage changes for China detected from GRACE data - Shanshan Hua; Hao Jing; Guoyu Qiu; Xingxing Kuang; Charles B. Andrews; Xi Chen; Chunmiao Zheng (Journal of Environmental Management, 2024)

Preconception mitochondrial DNA copy number plays a crucial role in linking prenatal air pollution with the risk of preterm birth - Qiuming Wang; Yalong Wang; Panpan Sun; Yanan He; Xi Yan; Lifang Jiang; Yuting Zeng; Jingjing Wu; Junxi Zhang; CuiPing Wu; Fangfang Yu; Yue Ba; et al. (International Journal of Hygiene and Environmental Health, 2024)

Role of galacturonic acid in acrylamide formation: Insights from structural analysis - Mengyi Lin; Guoyu Sun; Xiaosong Hu; Fang Chen; Yuchen Zhu (Food Chemistry, 2024)

Impaired neurogenesis induced by fluoride via the Notch1 signaling and effects of carvacrol intervention - Yuhui Du; Zichen Feng; Minghui Gao; Anqi Wang; Xi Yan; Ruiqin Chen; Bin Liu; Fangfang Yu; Yue Ba; Guoyu Zhou (Environmental Pollution, 2024)

Nontoxic and proteolytic-resistant self-assembled peptide dendrimer aggregates to combat multidrug-resistant gram-negative bacterial infections - Zhenheng Lai; Xiaojie Yuan; Guoyu Li; Hongyu Chen; Baojing Cheng; Anshan Shan (Chemical Engineering Journal, 2024)

The relationship between elevation-dependent warming and long-term trend of surface air temperature lapse rate - Yun Qin; Guoyu Ren; Lixiu Wu; Panfeng Zhang (Atmospheric Research, 2024)

Reclamation of coastal wetland to paddy soils alters the role of bacteria and fungi in nitrous oxide emissions: Evidence from a 53-year reclamation chronosequence study - Cheng Chen; Han Wu; Chuangchuang Li; Guoyu Yin; Tianyu Yin; Jiongyu Pan; Xia Liang; Xiaofei Li; Yanling Zheng; Lijun Hou; Min Liu (Agriculture, Ecosystems & Environment, 2024)

Synergetic sludge conditioning by US enhanced Fe2+ activated sodium persulfate: Physicochemical properties and mechanisms - Zhiying Lv; Hong You; Mingze Xu; Haoran Leng; Weirun Li; Yihan Zhao; Zhipeng Li; Jing Zhu; Guoyu Zhang (Chemosphere, 2024)

Novel design of simplified β-hairpin antimicrobial peptide as a potential food preservative based on Trp-pocket backbone - Changxuan Shao; Yuanmengxue Wang; Guoyu Li; Hongrui Guan; Yongjie Zhu; Licong Zhang; Na Dong; Anshan Shan (Food Chemistry, 2024)

Six‐decade trend in minute‐scale short‐duration intense precipitation in Beijing and its association with urbanization - Lingli Wang; Guoyu Ren; Yunjian Zhan (International Journal of Climatology, 2024)
Understanding the characteristics of minute‐scale short‐duration intense rainfall and its possible link with urbanization is valuable for addressing urban climate change and evaluating biases in high‐resolution historical precipitation data series. This study analyses the long‐term trends of rainy‐season minute‐scale intense rainfall events at different continuous time periods based on precipitation data from 20 national meteorological stations in the Beijing area covering the period from 1961 to 2021. This study shows that during the whole period analysed, the number of events of intense rainfall lasting 15 min or longer decreased, while the number of shorter‐duration events and the accumulated precipitation increased. The frequency and amount of minute‐scale intense rainfall recorded by urban stations are generally higher than those recorded by rural stations in terms of climatological means. The signal of the urbanization effect in minute‐scale precipitation changes is detectable, with the contribution of urbanization to the trends in average precipitation of 30‐min intense rainfall being 68.8%, whereas the contributions with respect to the frequency of 20‐ and 30‐min intense rainfall and the maximum precipitation of intense rainfall with a duration of 45 min reach 100%. The results of the analysis can provide reference for understanding long‐term changes in short‐duration rainfall and the possibility that they are driven by local anthropogenic activity, as well as bias in the minute‐scale precipitation data series of urban observation sites when they are used in studies of large‐scale intense precipitation changes.

An innovative segment anything model for precision poultry monitoring - Xiao Yang; Haixing Dai; Zihao Wu; Ramesh Bahadur Bist; Sachin Subedi; Jin Sun; Guoyu Lu; Changying Li; Tianming Liu; Lilong Chai (Computers and Electronics in Agriculture, 2024)

Implementation barriers to the circular supply chain mode for pre-consumer textile waste reprocessing in China - Guoyu Chen; Duanyang Geng; Qinghua Zhu (Resources, Conservation and Recycling, 2024)

Natural products with potential hypoglycemic activity in T2DM: 2019–2023 - Zhang Fei; Yang Xu; Guoyu Zhang; Yang Liu; Hua Li; Lixia Chen (Phytochemistry, 2024)

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Permafrost thawing caused by the China-Russia Crude oil pipeline based on multi-type data and its impacts on geomorphological reshaping and water erosion - Kai Gao; Guoyu Li; Yapeng Cao; Chunqing Li; Dun Chen; Gang Wu; Qingsong Du; Fei Wang; Fedorov Alexander; Fuqiang Che; Zhenrong Zhang; Luyao Bai; et al. (CATENA, 2024)

Reindeer (Rangifer tarandus) hindlimb joint kinetics: propulsive and energy storage mechanisms and mechanical work - Guoyu Li; Rui Zhang; Hao Pang; Junfeng Wang; Dan Jin; Xumin Sun; Dianlei Han; Zhisong Li; Lige Wen (Polar Biology, 2024)

Risk of heavy metal(loid) compositions in fine particulate matter on acute cardiovascular mortality: a poisson analysis in Anyang, China - Chaofan Shi; Jianjun Zhi; Hongsheng Zhao; Wan Wang; Hongjin Zhang; Guoyu Zhou; Xiaoli Fu; Yue Ba (International Journal of Biometeorology, 2024)

Thermal performance of a novel traditional Chinese personal heating device (Huotong) combined with PCMs - Wei Wei; Xuhui Cao; Guoyu Zhang; Guoji Zhang; Bendong Yu; Niansi Li; Jie Ji (Energy and Buildings, 2024)

Composite porous 3D foam for solar-driven atmospheric water harvesting in low humidity natural environment - Jiyan Li; Guoyu Xing; Min Qiao; Silu Du; Tao Zhou; Shuo Gao; Hanxue Sun; Rui Jiao; An Li (Chemical Engineering Journal, 2024)

Mediation of mitochondrial DNA copy number and oxidative stress in fluoride-related bone mineral density alteration in Chinese farmers - Yue Ba; Zichen Feng; Xiaoli Fu; Ruiqin Chen; Xuecheng Jiao; Yuhui Du; Xiaoxue Liu; Hui Huang; Fangfang Yu; Guoyu Zhou (Environmental Geochemistry and Health, 2024)

Water-soluble essential oil components of flowers of Paeonia × suffruticosa cultivars and in silico analysis with antidepressant targets - Gaoming Lei; Guoyu Gao; Mengke Zhou; Jianqi Guo; Yuting Chen (Natural Product Research, 2024)

Adjustment of the urbanization bias in surface air temperature series based on urban spatial morphologies and using machine learning - Tao Shi; Yuanjian Yang; Ping Qi; Guoyu Ren; Xiangcheng Wen; Chaman Gul (Urban Climate, 2024)

Is milk fat globule size correlated with milk fat content in Ruminants? - Menglu Zhang; Zhentao Liu; Fangyuan Kang; Kuixian Wu; Han Ni; Yingqian Han; Yanbin Yang; Tong Fu; Guoyu Yang; Tengyun Gao; Liqiang Han (Food Chemistry, 2024)

A creep model for soil-rock mixture considering the effect of rock contents and freeze-thaw cycles - Peiyong Qiu; Liyun Tang; Pengyu Wang; Jianguo Zheng; Weibing Wang; Yongqiang Li; Guoyu Li; Long Jin; Yongtang Yu; Xu Duan (Engineering Geology, 2024)

Unveiling the dual tunability of dimension and pore structure in MAX-derived carbon via molten salt electrolysis - Sheng Pang; Jijun Lu; Liangwei Cong; Youpeng Xu; Yiwei Sun; Zhenqian Zhang; Jianwei Guo; Dong Wang; Xiao Yang; Guoyu Qian; Zhi Wang (Chemical Engineering Journal, 2024)

Study on the characterization method and evolution law of the three-dimensional pore structure in frozen loess under loading - Shijie Chen; Wei Ma; Guoyu Li; Juan Li; Xiaoli Ma (Cold Regions Science and Technology, 2024)

Unveiling activation mechanism of persulfate by homologous hemp-derived biochar catalysts for enhanced tetracycline wastewater remediation - Chengyang Tang; Chuanyi Xu; Guoyu Zhong; Zhan Cen; Zhuobiao Ni; Zuofang Yao; Yueping Fang; Rongliang Qiu; Shengsen Zhang (Bioresource Technology, 2024)

A novel catalytic/sterilization PV-Trombe wall system: Analysis on PV electrical and air purification performance in winter - Lei Che; Niansi Li; Miaomiao Fan; Guoji Zhang; Guoyu Zhang; Bendong Yu (Building and Environment, 2024)

A sensitive and versatile electrochemical sensor based on hybridization chain reaction and CRISPR/Cas12a system for antibiotic detection - Xuemei Zhang; Li Zhu; Li Yang; Guoyu Liu; Shan Qiu; Xiaoli Xiong; Ke Huang; Ting Xiao; Liping Zhu (Analytica Chimica Acta, 2024)

Social-ecological network of peri-urban forest in urban expansion: A case study of urban agglomeration in Guanzhong Plain, China - Guoyu Wang; Jing Li; Xianfeng Liu; Boyan Li; Ya Zhang (Land Use Policy, 2024)

Novel application of high temperature solution growth method in simultaneously preparing SiC/Ti3SiC2/TiC using photovoltaic Si waste and Ti-bearing blast furnace slag - Sheng Pang; Hao Wang; Guoyu Qian; Yiwei Sun; Wenlong Fu; Jijun Lu; Zhilin Sheng; Zhi Wang (Journal of Cleaner Production, 2024)

Effective decapsulation method for photovoltaic modules: Limonene-induced EVA controlled swelling under sonication and debonding mechanism analysis - Rui Min; Weikai Deng; Zhi Wang; Tao Qi; Zhihan Zhang; Wanhai Xiao; Guoyu Qian; Dong Wang (Journal of Cleaner Production, 2024)

Performance analysis on a wood-color thermal catalytic Trombe wall in wood buildings - Huabo Wu; Niansi Li; Guoyu Zhang; Guoji Zhang; Jie Ji; Bendong Yu (Energy and Buildings, 2024)

Single Photon Detection Technology in Underwater Wireless Optical Communication: Modulation Modes and Error Correction Coding Analysis - Lei Gai; Wendong Li; Guoyu Wang (Journal of Ocean University of China, 2024)

Effect of short-term exposure to air pollution on hospital admission for cardiovascular disease: A time-series study in Xiangyang, China - Yangwenhao Liu; Meng Guo; Junxiang Wang; Yongxiang Gong; Chunrong Huang; Wei Wang; Xiaodong Liu; Juming Liu; Changyu Ju; Yue Ba; Guoyu Zhou; Xiaolin Wu (Science of The Total Environment, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Urban agglomerations as an environmental dimension of antibiotics transmission through the “One Health” lens - Fangfang Ding; Ye Li; Tianhao He; Dongni Ou; Ye Huang; Guoyu Yin; Jing Yang; Shixue Wu; Erkai He; Min Liu (Journal of Hazardous Materials, 2024)

Deep integration of pyrolysis kinetics and pyrolysis mechanism of polyimide aerogels - Xiangming Hu; Hongbin Wei; Yurui Deng; Zhiyuan Yang; Xiaoxuan Wei; Guoyu Han (Fuel, 2024)

U-shaped relationship between ozone exposure and preterm birth risk associated with preconception telomere length - Guoyu Zhou; Jian Chai; Qinyang Li; Panpan Sun; Yalong Wang; Jingjing Wu; Junxi Zhang; Yan Li; Wei Dong; Cuican Zhang; Fangfang Yu; Xi Yan; et al. (Environmental Pollution, 2024)

Degrading permafrost beneath road embankments of the Qinghai-Tibet Highway from 1995 to 2020 - Zhizhong Sun; Wei Ma; Guoyu Li; Yongzhi Liu; Guilong Wu (Cold Regions Science and Technology, 2024)

Experimental study on the dealkalization of red mud using the freeze-thaw and acid washing method - Dahu Rui; Mingpu Li; Mintae Kim; Jun Zhang; Wenjun Nie; Shuren Wang; Guoyu Li; Shengjie Liu (Cold Regions Science and Technology, 2024)

Rapid permafrost thaw under buried oil pipeline and effective solution using a novel mitigative technique based on field and laboratory results - Yapeng Cao; Wei Ma; Guoyu Li; Kai Gao; Changqing Li; Dun Chen; Yunhu Shang; Xiaobin Wei; Zhixiang Chen; Gang Wu; Pengchao Chen; Luyao Bai; et al. (Cold Regions Science and Technology, 2024)

Extreme rainfall events variation during 1860–1909 in the Korean Peninsula: Investigation of the possible circulation mechanism by a method of analogue - Kum-Chol Om; Ren GuoYu; Sang-Il Jong; O. Hyon-Ok; Song-Il Kim; O. Kang-Chol (Atmospheric Research, 2024)

Distinctive species interaction patterns under high nitrite stress shape inefficient denitrifying phosphorus removal performance - Xue Wang; Guoyu Zhang; Aizhong Ding; En Xie; Qiuyang Tan; Yuzi Xing; Haoming Wu; Qi Tian; Yaoxin Zhang; Lei Zheng (Bioresource Technology, 2024)

Performance analysis of microbial fuel cell - membrane bioreactor with reduced graphene oxide enhanced polypyrrole conductive ceramic membrane: Wastewater treatment, membrane fouling and microbial community under high salinity - Rui Wang; Hong You; Binghan Xie; Guoyu Zhang; Jing Zhu; Weirun Li; Xinan Dong; Qiqing Qin; Mengying Wang; Yi Ding; Haili Tan; Yuhong Jia; et al. (Science of The Total Environment, 2024)

Non-radical mediated reduced graphene oxide/polypyrrole catalytic ceramic membrane-PDS system for source control of SMX - Rui Wang; Hong You; Zhipeng Li; Jing Zhao; Mu Li; Jing Zhu; Guoyu Zhang; Xianshi Wang; Haoran Leng; Shaojie Qi; Binghan Xie (Chemical Engineering Journal, 2024)

Experimental investigations on the shear strength and creep properties of soil-rock mixture under freeze-thaw cycles - Peiyong Qiu; Liyun Tang; Jianguo Zheng; Weibing Wang; Yongqiang Li; Guoyu Li; Long Jin; Yongtang Yu; Xu Duan (Cold Regions Science and Technology, 2024)

The establishment of the priority right in space resources activities - Guoyu Wang; Xinyi Huang (Advances in Space Research, 2024)

Effect of zinc intake on association between fluoride exposure and abnormal sex steroid hormones among US pubertal males: NHANES, 2013–2016 - Zeyuan Niu; Leizhen Duan; Yuhui Du; Fangfang Yu; Ruiqin Chen; Zhiyuan Li; Yue Ba; Guoyu Zhou (Environmental Science and Pollution Research, 2023)

Community pattern of potential phenanthrene (PHE) degrading bacteria in PHE contaminated soil revealed by 13C-DNA stable isotope probing - Xiufeng Tang; Ye Li; Ruihe Jin; Guoyu Yin; Lijun Hou; Min Liu; Feng Ju; Ping Han (Chemosphere, 2023)

A dynamic constrained multiobjective evolutionary algorithm based on decision variable classification - Yinan Guo; Mingyi Huang; Guoyu Chen; Dunwei Gong; Jing Liang; Zekuan Yu (Swarm and Evolutionary Computation, 2023)

Record-breaking marine heatwave in northern Yellow Sea during summer 2018: Characteristics, drivers and ecological impact - Yan Li; Guoyu Ren; Qingyuan Wang; Lin Mu; Qianru Niu; Hanxiang Su (Science of The Total Environment, 2023)

The bioaerosols generated from the sludge treatment process: Bacterial and fungal variation characteristics, source tracking, and risk assessment - Yanjie Wang; Yang Liu; Kai Yang; Liying Yang; Song Zhang; Yue Ba; Guoyu Zhou (Science of The Total Environment, 2023)

Preparation and characterization of nano-SiO2-modified emulsified film and its application for strawberry preservation - Yuxin Jiang; Guoyu Zhao; Xiaoling Yang; Fangyu Fan (Food Packaging and Shelf Life, 2023)

Macroscopic and mesoscopic comparative study of frozen loess under loading and unloading - Shijie Chen; Wei Ma; Guoyu Li; Peng Zhang (Cold Regions Science and Technology, 2023)

Experimental study on the influence of sandstone gradation on the water storage capacity of a pore-space reservoir in a waste dump of an open-pit coal mine - Jingwei Wang; Shuzhao Chen; Liu Han; Tao Shang; Shouhe Cao; Guoyu Yang; Tao Chen; Yinda Li (Hydrogeology Journal, 2023)

Exploring regional ecological compensation of cultivated land from the perspective of the mismatch between grain supply and demand - Dan Su; Jiayi Wang; Qing Wu; Xiaoqian Fang; Yu Cao; Guoyu Li; Yu CAO (Environment, Development and Sustainability, 2023)

Uncovering scale effects on spatial patterns and interactions of multiple cropland ecosystem services - Yu Cao; Dan Su; Jiayi Wang; Guoyu Li; Xiaoqian Fang; Qing Wu; Yu Cao (Environment, Development and Sustainability, 2023)

Spatial-temporal characteristics of the urban heat island effect in Xiamen, China - Jia Wenqian; Ren Guoyu; Jin Fengjun; He Jiajun; Zhang Panfeng (Urban Climate, 2023)

Tidal dynamics regulates potential coupling of carbon‑nitrogen‑sulfur cycling microbes in intertidal flats - Yuhui Niu; Zhirui An; Dengzhou Gao; Feiyang Chen; Jie Zhou; Bolin Liu; Lin Qi; Li Wu; Zhuke Lin; Guoyu Yin; Xia Liang; Hongpo Dong; et al. (Science of The Total Environment, 2023)

Vortex-induced vibration at low Reynolds numbers: Vortex shedding modes transitions - Haidong Zhao; Hao Ding; Chao Wang; Ke Li; Guoyu Wang; Bing Ren (Ocean Engineering, 2023)

Glass phase extraction for one-step separation and recovery of strategic metals from spent hydrofining catalysts - Yuanyuan Cai; Zuoren Nie; Xiaoli Xi; Yue Lu; Yajiao Zhang; Guoyu Huang; Caijuan Shi; Lu Deng; Zhiyong Zhao; Yingliang Tian (Chemical Engineering Journal, 2023)

Realizing high thermoelectric performance in p-type CaZn2Sb2-alloyed Mg3Sb2-based materials via band and point defect engineering - Lian Wu; Zizhen Zhou; Guang Han; Bin Zhang; Jian Yu; Hengyang Wang; Yao Chen; Xu Lu; Guoyu Wang; Xiaoyuan Zhou (Chemical Engineering Journal, 2023)

Field observations on hydro-thermal regimes of loess cut slopes in cold and arid regions: A comparative study of sunny and shady slopes - Kun Zhang; Dongna Li; Yanhu Mu; Guoyu Li; Hongjuan Wu; Yuncheng Mao; Li Li; Qinglong Zhang (Cold Regions Science and Technology, 2023)

Do carbon sequestration and food security in urban and rural landscapes differ in patterns, relationships, and responses? - Ya Zhang; Jing Li; Xianfeng Liu; Jizhou Bai; Guoyu Wang (Applied Geography, 2023)

Ball-milled sulfide iron-copper bimetals based composite permeable materials for Cr (VI) removal: Effects of preparation parameters and kinetics study - Zhenghan Yang; Guoyu Ding; Lili Yan; Runkai Wang; Wenqi Zhang; Xingrun Wang; Pinhua Rao (Chemosphere, 2023)

Effects of microplastics on denitrification and associated N2O emission in estuarine and coastal sediments: insights from interactions between sulfate reducers and denitrifiers - Cheng Chen; Guoyu Yin; Qiuxuan Li; Youran Gu; Dongyao Sun; Soonmo An; Xia Liang; Xiaofei Li; Yanling Zheng; Lijun Hou; Min Liu (Water Research, 2023)

Developing self-floating N-defective graphitic carbon nitride photocatalyst for efficient photodegradation of Microcystin-LR under visible light - Xin Li; Guoyu Li; Meifang Li; Xiaodong Ji; Chunfang Tang; Xiaohua Fu; Honghui Jiang; Xiaofei Tan; Hui Wang; Xinjiang Hu (Science of The Total Environment, 2023)

Ply angle effects on cavitating flow induced structural response characteristics of the composite hydrofoils - Miaomiao Ji; Housheng Zhang; Qin Wu; Hanzhe Zhang; Biao Huang; Guoyu Wang (Ocean Engineering, 2023)

Strategic nitrogen defect engineering for optimizing the photocatalytic performance of polymerized carbon nitride: Identification, synthesis, and mechanism - Zhangkai Chen; Meifang Li; Xinjiang Hu; Yuan Yuan; Hui Wang; Jiaqin Deng; Xiaodong Ji; Guoyu Li; Yuan Ouyang; Ni Liu (Journal of Environmental Chemical Engineering, 2023)

Benzeneboronic−alginate/quaternized chitosan−catechol powder with rapid self-gelation, wet adhesion, biodegradation and antibacterial activity for non-compressible hemorrhage control - Yan Du; Xingtao Chen; Lin Li; Heng Zheng; Aiping Yang; Hong Li; Guoyu Lv (Carbohydrate Polymers, 2023)

Programmable electrochemical biosensing platform based on catalytic hairpin assembly and entropy-driven catalytic cascade amplification circuit - Liping Zhu; Li Zhu; Xuemei Zhang; Li Yang; Guoyu Liu; Xiaoli Xiong (Analytica Chimica Acta, 2023)

Synergistic removal of Cd(II)-organic complexes by combined permanent magnetic resins - Xiang Wan; Guoyu Qiu; Adhean Yves-Gaël Gbahouo; Qimeng Li; Guoxiang Wang; Fei Yang (Chemosphere, 2023)

Permeability decides the effect of antibiotics on sedimentary nitrogen removal in Jiulong River Estuary - Ru Wan; Lianghao Ge; Bin Chen; Jin-Ming Tang; Ehui Tan; Wenbin Zou; Li Tian; Meng Li; Zongbao Liu; Lijun Hou; Guoyu Yin; Shuh-Ji Kao (Water Research, 2023)

Remediation of Cr(VI)-contaminated soil mixed with chromite ore processing residue by ferrous sulfate and enzyme residue - Kaiyu Shi; Yuxiu Zhang; Guoyu Ding; Xingrun Wang; Xianghua Yan; Hong Pan; Yuan Zhao (Science of The Total Environment, 2023)

Toward sustainability for upcycling SoG-Si scrap by an immersion rotational segregation purification process - Guoyu Qian; Lu Zhou; Jijun Lu; Sheng Pang; Yiwei Sun; Jiachen Pang; Dong Wang; Kuixian Wei; Wenhui Ma; Zhi Wang (Journal of Cleaner Production, 2023)

Complexation of copper algaecide and algal organic matter in algae-laden water: Insights into complex metal–organic interactions - Fei Yang; Yun Hu; Guoyu Qiu; Qimeng Li; Guoxiang Wang (Environmental Pollution, 2023)

Evaluation of ground surface deformation in discontinuous permafrost regions along the China-Russia Crude Oil Pipelines in Northeast China using InSAR and ground surveys - Wenhui Wang; Xiaoying Jin; Huijun Jin; Xinyu Li; Xinbin Wang; Ruixia He; Yan Li; Xiaoying Li; Lizhong Wang; Wei Wang; Changlei Wei; Gangyi Zhou; et al. (Engineering Geology, 2023)

Typhoon-related changes in moisture pathways and sources for precipitation in Eastern China during the three major rainy seasons - Jinning Che; Bo Liu; Lei Chen; Guoyu Ren; Tianjun Zhou (Atmospheric Research, 2023)

Recycling of solar cells from photovoltaic modules via an environmentally friendly and controllable swelling process by using dibasic ester - Ke Li; Dong Wang; Kaibo Hu; Changming Liu; Zhi Wang; Guobiao Li; Xuanyi Chen; Guoyu Qian (Clean Technologies and Environmental Policy, 2023)

Thermal performance and heat transfer process of an expressway embankment with horizontal-thermosyphons in permafrost regions - Kun Chen; Mingyang Jin; Guoyu Li; Youqian Liu; Jinxin Lu; Yaojun Zhao; Qihao Yu (Cold Regions Science and Technology, 2023)

Study on eco-efficiency of cultivated land utilization based on the improvement of ecosystem services and emergy analysis - Jiayi Wang; Dan Su; Qing Wu; Guoyu Li; Yu Cao (Science of The Total Environment, 2023)

Anthropogenic land-use activities within watersheds reduce comammox activity and diversity in rivers - Qiuyang Tan; Guoyu Zhang; Aizhong Ding; Zhaoyong Bian; Xue Wang; Yuzi Xing; Lei Zheng (Journal of Environmental Management, 2023)

In-doping induced resonant level and thermoelectric performance enhancement in n-type GeBi2Te4 single crystals with intrinsically low lattice thermal conductivity - Peng Chen; Bin Zhang; Hanjun Zou; Xiangnan Gong; Yanci Yan; Jingwei Li; Daliang Zhang; Guang Han; Xu Lu; Hong Wu; Yun Zhou; Xiaoyuan Zhou; et al. (Chemical Engineering Journal, 2023)

TaMADS29 interacts with TaNF-YB1 to synergistically regulate early grain development in bread wheat - Guoyu Liu; Runqi Zhang; Sen Li; Rehmat Ullah; Fengping Yang; Zihao Wang; Weilong Guo; Mingshan You; Baoyun Li; Chaojie Xie; Liangsheng Wang; Jie Liu; et al. (Science China Life Sciences, 2023)

Saltwater incursion regulates N2O emission pathways and potential nitrification and denitrification in intertidal wetland - Yinghui Jiang; Guoyu Yin; Ye Li; Lijun Hou; Min Liu; Cheng Chen; Dongsheng Zheng; Han Wu; Dengzhou Gao; Yanling Zheng; Ping Han (Biology and Fertility of Soils, 2023)

Potential response of dark carbon fixation to global warming in estuarine and coastal waters - Lin Qi; Yanling Zheng; Lijun Hou; Bolin Liu; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Global Change Biology, 2023)
Dark carbon fixation (DCF), through which chemoautotrophs convert inorganic carbon to organic carbon, is recognized as a vital process of global carbon biogeochemical cycle. However, little is known about the response of DCF processes in estuarine and coastal waters to global warming. Using radiocarbon labelling method, the effects of temperature on the activity of chemoautotrophs were investigated in benthic water of the Yangtze estuarine and coastal areas. A dome‐shaped thermal response pattern was observed for DCF rates (i.e., reduced rates at lower or higher temperatures), with the optimum temperature ( T opt ) varying from about 21.9 to 32.0°C. Offshore sites showed lower T opt values and were more vulnerable to global warming compared with nearshore sites. Based on temperature seasonality of the study area, it was estimated that warming would accelerate DCF rate in winter and spring but inhibit DCF activity in summer and fall. However, at an annual scale, warming showed an overall promoting effect on DCF rates. Metagenomic analysis revealed that the dominant chemoautotrophic carbon fixation pathways in the nearshore area were Calvin‐Benson‐Bassham (CBB) cycle, while the offshore sites were co‐dominated by CBB and 3‐hydroxypropionate/4‐hydroxybutyrate cycles, which may explain the differential temperature response of DCF along the estuarine and coastal gradients. Our findings highlight the importance of incorporating DCF thermal response into biogeochemical models to accurately estimate the carbon sink potential of estuarine and coastal ecosystems in the context of global warming.

Microbial necromass carbon in estuarine tidal wetlands of China: Influencing factors and environmental implication - Jine Wei; Fenfen Zhang; Dongliang Ma; Jing Zhang; Yanling Zheng; Hongpo Dong; Xia Liang; Guoyu Yin; Ping Han; Min Liu; Lijun Hou (Science of The Total Environment, 2023)

Preparation of porous C3N5 nanosheets by temperature modulation: Visible-light induced degradation characteristics and mechanism of microcystin-LR - Qizhuo Liu; Xiaodong Ji; Jiaqin Deng; Honghui Jiang; Guoyu Li; Yuanhao Ouyang; Xin Li; Chunfang Tang; Xiaofei Tan; Xinjiang Hu (Journal of Environmental Chemical Engineering, 2023)

Membrane biofouling mitigation via immobilizing AgNPs@ZIF-8 microcapsules on membrane surface for extractive membrane bioreactor - Bingxin Wang; Yuxiao Tian; Tingting Yang; Guoyu Yuan; Xiangjun Liao; Xiaofei You; Yuan Liao (Journal of Environmental Chemical Engineering, 2023)

The characteristic evolution and formation mechanism of hybrid microalgae biofilm and its application in mariculture wastewater treatment - Yanbo Liu; Guoyu Zhang; Weirun Li; Yi Ding; Hong You; Jing Zhu; Haoran Leng; Chi Xu; Xiaodi Xing; Jingyue Xu; Zhipeng Li (Journal of Environmental Chemical Engineering, 2023)

Nitrite-resistance mechanisms on wastewater treatment in denitrifying phosphorus removal process revealed by machine learning, co-occurrence, and metagenomics analysis - Xue Wang; Guoyu Zhang; Aizhong Ding; Lei Zheng; En Xie; Dongdan Yuan; Qiuyang Tan; Yuzi Xing; Haoming Wu (Environmental Pollution, 2023)

Correction to: The whole genomic analysis of the Orf virus strains ORFV‑SC and ORFV‑SC1 from the Sichuan province and their weak pathological response in rabbits - Guoyu Du; Jinyan Wu; Cheng Zhang; Xiaoan Cao; Lingxia Li; Jijun He; Yong Zhang; Youjun Shang (Functional & Integrative Genomics, 2023)

The whole genomic analysis of the Orf virus strains ORFV-SC and ORFV-SC1 from the Sichuan province and their weak pathological response in rabbits - Guoyu Du; Jinyan Wu; Cheng Zhang; Xiaoan Cao; Lingxia Li; Jijun He; Yong Zhang; Youjun Shang (Functional & Integrative Genomics, 2023)
The Orf virus (ORFV) is a member of the Parapoxvirus genus of the Poxviridae family and can cause contagious diseases in sheep, goats, and wild ungulates. In the present study, two ORFV isolates (ORFV-SC isolated from Sichuan province and ORFV-SC1 produced by 60 passages of ORFV-SC in cells) were sequenced and compared to multiple ORFVs. The two ORFV sequences had entire genome sizes of 14,0707 bp and 141,154 bp, respectively, containing 130 and 131 genes, with a G + C content of 63% for the ORFV-SC sequence and 63.9% for the ORFV-SC1 sequence. Alignment of ORFV-SC and ORFV-SC1 with five other ORFV isolates revealed that ORFV-SC, ORFV-SC1, and NA1/11 shared > 95% nucleotide identity with 109 genes. Five genes (ORF007, ORF20, ORF080, ORF112, ORF116) have low amino acids identity between ORFV-SC and ORFV-SC1. Mutations in amino acids result in changes in the secondary and tertiary structure of ORF007, ORF020, and ORF112 proteins. The phylogenetic tree based on the complete genome sequence and 37 single genes revealed that the two ORFV isolates originated from sheep. Finally, animal experiments demonstrated that ORFV-SC1 is less harmful to rabbits than ORFV-SC. The exploration of two full-length viral genome sequences provides valuable information in ORFV biology and epidemiology research. Furthermore, ORFV-SC1 demonstrated an acceptable safety profile following animal vaccination, indicating its potential as a live ORFV vaccine.

Diversified land conversion deepens understanding of impacts of rapid rubber plantation expansion on plant diversity in the tropics - Bangqian Chen; Jun Ma; Chuan Yang; Xiangming Xiao; Weili Kou; Zhixiang Wu; Ting Yun; Zar Ni Zaw; Piyada Nawan; Ratchada Sengprakhon; Jiannan Zhou; Jikun Wang; et al. (Science of The Total Environment, 2023)

A dual risk perspective of China's resources market: Geopolitical risk and political risk - Guoyu Wang; Xiao Gu; Xi Shen; Khusniddin Fakhriddinovich Uktamov; Mohammed Moosa Ageli (Resources Policy, 2023)

Integrating temperature gradient-based 3T and resistance-based models for simulating evapotranspiration and its components - Pei Wang; Dapeng Zhang; Yuhua Xing; Xiao-Yan Li; Guoyu Qiu; Xiuchen Wu; Haitao Sun; Yujiu Xiong; Lixin Wang (Journal of Hydrology, 2023)

Classification of Pericarpium Citri Reticulatae (Chenpi) age using surface-enhanced Raman spectroscopy - Guoyu Dai; Longxiang Wu; Jianhua Zhao; Qiunong Guan; Haishan Zeng; Ming Zong; Manqin Fu; Caigan Du (Food Chemistry, 2023)

Construction of g-C3N4 with N2C-type defects/MoO3 Z-scheme photocatalyst: Effective mineralization and toxicity reduction of microcystin-LR by multiple free radical degradation pathways - Yuanhao Ouyang; Honghui Jiang; Haoxiang Zhong; Guoyu Li; Xiaodong Ji; Qi Jin; Wei Xue; Xinjiang Hu; Mingshan Zhu (Chemical Engineering Journal, 2023)

Reconstruction and characterization of droughts and floods in the Hanjiang River Basin, China, 1426–2017 - Xiaodan Zhang; Guoyu Ren; He Bing; Takehiko Mikami; Jun Matsumoto; Panfeng Zhang; Guowei Yang (Climatic Change, 2023)

Synergetic control of heterogeneous nucleation and 3D mixed electron/ion-conducting paths for dendrite-free Li metal anodes - Chengzhou Ye; Zhongyong Zhang; Junjie Li; Weiwei Jiang; Guoyu Ding; Wenji Li; Jing Zhang; Long Huang; Zhihao Yue; Naigen Zhou; Fugen Sun (Chemical Engineering Journal, 2023)

Applicability analysis of thermosyphon for thermally stabilizing pipeline foundation permafrost and its layout optimization - Fei Wang; Guoyu Li; Fedorov Alexander; Wei Ma; Dun Chen; Gang Wu; Yanhu Mu; Xinbin Wang; Hongyuan Jing; Zhenrong Zhang (Cold Regions Science and Technology, 2023)

Research on the Critical Buckling Pressure of Bucket Foundations with Inner Compartments for Offshore Wind Turbines - Guodong Sun; Run Liu; Qingxin Li; Guoyu Huang; Zhenbo Zhou; Cheng Zhang (Journal of Ocean University of China, 2023)

Dynamic changes in urban land spatial inequality under the core-periphery structure in urban agglomerations - Xiaoqian Fang; Dan Su; Qing Wu; Jiayi Wang; Yangjian Zhang; Guoyu Li; Yu Cao (Journal of Geographical Sciences, 2023)

Association between dental fluorosis prevalence and inflammation levels in school-aged children with low-to-moderate fluoride exposure - Huayang Tang; Mengru Wang; Gaochun Li; Mengwei Wang; Chen Luo; Guoyu Zhou; Qian Zhao; Lixin Dong; Hongliang Liu; Yushan Cui; Li Liu; Shun Zhang; et al. (Environmental Pollution, 2023)

Multibiofunctional TFEB-engineered endothelial progenitor cell-derived extracellular vesicles/hydrogel system for rescuing critical limb ischemia - Chen Zhao; Zheng Xing; Xinbo Wei; Guoyu Liao; Depeng Yang; Haifeng Liu; Yubo Fan (Chemical Engineering Journal, 2023)

Nitrogen loss from anaerobic ammonium oxidation coupled to Iron(III) reduction activity across estuarine and coastal wetlands of China: Spatial variations, controlling factors, and environmental implications - Shuntao Chen; Dengzhou Gao; Xiaofei Li; Dongyao Sun; Yanling Zheng; Hongpo Dong; Xia Liang; Guoyu Yin; Ping Han; Min Liu; Lijun Hou (CATENA, 2023)

Substantial increase in human-perceived heatwaves in eastern China in a warmer future - Jintao Zhang; Qinglong You; Guoyu Ren; Safi Ullah (Atmospheric Research, 2023)

A coupled CEEMD-BiLSTM model for regional monthly temperature prediction - Xianqi Zhang; Yimeng Xiao; Guoyu Zhu; Jingwen Shi (Environmental Monitoring and Assessment, 2023)

Effects of periodic drying-wetting on microbial dynamics and activity of nitrite/nitrate-dependent anaerobic methane oxidizers in intertidal wetland sediments - Feiyang Chen; Yuhui Niu; Zhirui An; Li Wu; Jie Zhou; Lin Qi; Guoyu Yin; Hongpo Dong; Xiaofei Li; Dengzhou Gao; Min Liu; Yanling Zheng; et al. (Water Research, 2023)

Strong transient characteristics in axial flow waterjet pump during rapid starting period with special emphasis on saddle zone - Fengchuan Zheng; Xiaoping Zhang; Tairan Chen; Biao Huang; Jin Xu; Guoyu Wang (Ocean Engineering, 2023)

Magnetic biochar pyrolyzed from municipal sludge for Fenton-like degradation of thiamethoxam: Characteristics and mechanism - Zijie Zhang; Xinming Yang; Jin Wang; Tao Zhuang; Shurui Liu; Mengmeng Dou; Kaili Huo; Yanmei Zhou; Guoyu Ding (Journal of Water Process Engineering, 2023)

The deposition mapping of polycyclic aromatic hydrocarbons in megacity Shanghai, China - Ye Li; Ye Huang; Lina Yuan; Yue He; Guoyu Yin; Tianhao He; Erkai He; Fangfang Ding; Haibin Xia; Haoran Xu; Min Liu; Shu Tao (Journal of Hazardous Materials, 2023)

Estimating and forecasting the impact of nonrenewable energy prices on US renewable energy consumption - Bebonchu Atems; Jehu Mette; Guoyu Lin; Golshan Madraki (Energy Policy, 2023)

Non-concentrated electrolyte with weak anion coordination enables low Li-ion desolvation energy for low-temperature lithium batteries - Honglu Hu; Jinhan Li; Qiu Zhang; Guoyu Ding; Jiuding Liu; Yang Dong; Kang Zhao; Meng Yu; Huan Wang; Fangyi Cheng (Chemical Engineering Journal, 2023)

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

Analysis and research on the difference of design codes for vertical bearing capacity of pile foundation in cold regions - Liyun Tang; Yupeng Cui; Jianbing Chen; Gengshe Yang; Shiyuan Sun; Guoyu Li; Qiang Sun; Hailiang Jia (Cold Regions Science and Technology, 2023)

Simultaneous measurement of multiple labile heavy metals in soils by diffusive gradients in thin film technique - Rui Chen; Jiaxing Liu; Guoyu Ding; Fumin Ren; Rongguang Shi; Jungang Lv; Jing Cheng (Journal of Soils and Sediments, 2023)

Persulfate activation by sludge-derived biochar for efficient degradation of 2,4-dichlorophenol: performance and mechanism - Shurui Liu; Jin Wang; Zijie Zhang; Mengmeng Dou; Kaili Huo; Guoyu Ding; Yanmei Zhou; Chen Qiao (Environmental Science and Pollution Research, 2023)

Long-term over-the-horizon microwave channel measurements and statistical analysis in evaporation ducts over the Yellow Sea - Shuwen Wang; Kunde Yang; Yang Shi; Hao Zhang; Fan Yang; Dawei Hu; Guoyu Dong; Yihang Shu (Frontiers in Marine Science, 2023)
Maritime high-speed over-the-horizon wireless communication is realizable through evaporation ducts. Detailed measurement, analysis, and modeling of duct channels are essential for application of this communication technique. In this paper, X-band electromagnetic (EM) wave propagation systems were developed and deployed for a 133-km over-the-horizon microwave link in coastal areas of the Yellow Sea. The propagation length was 7.7 times the line-of-sight length. Measurement results including the path loss (PL) and meteorological data were obtained during a 54-day period in autumn 2021. The long-term channel results were analyzed on the basis of statistical analysis and model simulations. Results showed that our measurement system, with a maximum measurable power loss of 200 dB, had connected with a probability of 56.2% during the measurement period. Model simulation showed that evaporation duct environments are not ideal in autumn, with an average evaporation duct height (EDH) of 10.6 m. The land breeze in autumn introduced dry and cold air to the link, which could promote evaporation of seawater and reduce PL by approximately 40 dB. Annual spatiotemporal characteristics of EDH showed that evaporation ducts are most suitable for over-the-horizon communication in spring, especially May.

Improving flotation separation of micro Si/SiC particles from silicon sawing waste by surface hydrophilic modification - Dong Wang; Xuanyi Chen; Yong Hua; Zhi Wang; Changming Liu; Zhankui Wang; Guoyu Qian (Minerals Engineering, 2023)

Ultrafast sintering of Na3Zr2Si2PO12 solid electrolyte for long lifespan solid-state sodium ion batteries - Pengfeng Jiang; Guangyuan Du; Yuansheng Shi; Fengquan She; Pengqian Guo; Guoyu Qian; Xueyi Lu; Fangyan Xie; Xia Lu (Chemical Engineering Journal, 2023)

Characteristics, diffusion, and exposure risk of bioaerosol pollution during haze period on a campus of central China - Yanjie Wang; Song Zhang; Liying Yang; Huiling Song; Guoyu Zhou (Air Quality, Atmosphere & Health, 2023)

Extreme drought events diagnosed along the Yellow River and the adjacent area - Yongxiang Zhang; Hongli Wang; Xuemei Shao; Jinbao Li; Guoyu Ren (Climatic Change, 2022)

Phyllosphere fungal communities of rubber trees exhibited biogeographical patterns, but not bacteria - Yaqing Wei; Guoyu Lan; Zhixiang Wu; Bangqian Chen; Fei Quan; Mingmei Li; Shuqing Sun; Haonan Du (Environmental Microbiology, 2022)
Summary Phyllosphere microbiomes play an essential role in maintaining host health and productivity. Still, the diversity patterns and the drivers for the phyllosphere microbial community of the tropical cash crop Rubber tree ( Hevea brasiliensis ) – are poorly understood. We sampled the phyllosphere of field‐grown rubber trees in South China. We examined the phyllosphere bacterial and fungal composition, diversity and main drivers of these microbes using the Illumina® sequencing and assembly. Fungal communities were distinctly different in different climatic regions (i.e. Xishuangbanna and Hainan Island) and climatic factors, especially mean annual temperature, and they were the main driving factors of foliar fungal communities, indicating fungal communities showed a geographical pattern. Significant differences of phyllosphere bacterial communities were detected in different habitats (i.e. endophytic and epiphytic). Most of the differences in taxa composition came from Firmicutes spp., which have been assigned as nitrogen‐fixing bacteria. Since these bacteria cannot penetrate the cuticle like fungi, the abundant epiphytic Firmicutes spp. may supplement the deficiency of nitrogen acquisition. And the main factor influencing endophytic bacteria were internal factors, such as total nitrogen, total phosphorus and water content of leaves. External factors (i.e. climate) were the main driving force for epiphytic bacteria community assembly. Our work provides empirical evidence that the assembly of phyllosphere bacterial and fungal differed, which creates a precedent for preventing and controlling rubber tree diseases and pests and rubber tree yield improvement.

Effects of cement content and soil texture on strength, hydraulic, and microstructural characteristics of cement-stabilized composite soils - Shengnian Wang; Shuangfeng Guo; Xinqun Gao; Peng Zhang; Guoyu Li (Bulletin of Engineering Geology and the Environment, 2022)

Fracture Mechanical Properties of Frozen Sandstone at Different Initial Saturation Degrees - Ting Wang; Qiang Sun; Hailiang Jia; Yanjun Shen; Guoyu Li (Rock Mechanics and Rock Engineering, 2022)

Farnesoid X receptor (FXR) agonists induce hepatocellular apoptosis and impair hepatic functions via FXR/SHP pathway - Tianwei Zhang; Shanshan Feng; Jiahuan Li; Zhitao Wu; Qiangqiang Deng; Wei Yang; Jing Li; Guoyu Pan (Archives of Toxicology, 2022)

Hypoxia Stress Induces Tissue Damage, Immune Defense, and Oxygen Transport Change in Gill of Silver Carp (Hypophthalmichthys molitrix): Evaluation on Hypoxia by Using Transcriptomics - Xiaohui Li; Chen Ling; Qiaoxin Wang; Cui Feng; Xiangzhong Luo; Hang Sha; Guoyu He; Guiwei Zou; Hongwei Liang (Frontiers in Marine Science, 2022)
The silver carp ( Hypophthalmichthys molitrix ) is an economically, as well as environmentally, important fish that harbors low environmental hypoxia tolerance and frequently contributes to a loss of aquaculture productivity. The gill is the first tissue attacked by hypoxia; however, the response of the gills of H. molitrix to hypoxia stress at the tissue, cellular, and molecular levels has not been clearly established. The influence of hypoxia on histological features along with gene expression in silver carp gills were explored in this research. The hematoxylin and eosin-stained sections and electron microscopy examinations of gills indicated that the gill lamellae were seriously twisted, gill filaments were dehisced, and the swelling and shedding of epithelial cell layer in the gill tissue were intensified along with the degree of hypoxia. In the hypoxia, semi-asphyxia, and asphyxia groups, the gill transcriptomic assessment of shifts in key genes, as well as modulatory networks in response to hypoxic conditions revealed 587, 725, and 748 differentially expressed genes, respectively. These genes are abundant in immune response signaling cascades (e.g., complement and coagulation cascades, Nucleotide-binding and oligomerization domain (NOD)-like receptor signaling cascade, and differentiation of Th1 along with Th2 cells) and oxygen transport [e.g., MAPK, PI3K-Akt, and hypoxia-inducible factor 1 (HIF-1) signaling cascades]. Genes linked to immune response (e.g., c2 , c3 , c6 , klf4 , cxcr4 , cd45 , and cd40 ) and oxygen transport (e.g., egln1 , egln3 , epo , ldh , and vegfa ) were additionally identified. According to our findings, the silver carp may be using “HIF-1” to obtain additional oxygen during hypoxia. These findings illustrate that hypoxia stress might damage gill tissue, trigger an immunological response, and activate HIF-1 signaling to increase oxygen availability under hypoxic situations. The findings of this work will help scientists better understand the molecular mechanisms driving hypoxia responses in hypoxia-sensitive fish and speed up the development of hypoxia-resistant varieties.

New chemical constituents from the fruits of Tetradium ruticarpum - Xiulan Xin; Bo Shao; Ye Li; Shasha Liu; Dawei Li; Chao Wang; Liang Chen; Lihua Jin; Xiaochi Ma; Guoyu Wu (Natural Product Research, 2022)

NPC1-regulated dynamic of clathrin-coated pits is essential for viral entry - Guoli Li; Bingqian Su; Pengfei Fu; Yilin Bai; Guangxu Ding; Dahua Li; Jiang Wang; Guoyu Yang; Beibei Chu (Science China Life Sciences, 2022)

Shifting from homogeneous to heterogeneous surfaces in estimating terrestrial evapotranspiration: Review and perspectives - Yuanbo Liu; Guoyu Qiu; Hongsheng Zhang; Yonghui Yang; Yinsheng Zhang; Quan Wang; Wenzhi Zhao; Li Jia; Xibin Ji; Yujiu Xiong; Chunhua Yan; Ning Ma; et al. (Science China Earth Sciences, 2022)

Transgelin-2 interacts with CD44 to regulate Notch1 signaling pathway and participates in colorectal cancer proliferation and migration - Rong Ding; Guoyu Li; Yueyi Yao; Lijuan Zhang; Xuan Zhang; Jiayi Li; Tao Shen; Yi Gao; Tao Wu; Shuzhen Kong; Ming Huang; Yunfeng Li (Journal of Physiology and Biochemistry, 2022)

The neonatal PROC gene rs1799809 polymorphism modifies the association between prenatal air pollutants exposure and PROC promoter methylation - Zhiyuan Li; Meng Yang; Leizhen Duan; Yongxiang Gong; Hongxia Xia; Francis-Kojo Afrim; Hui Huang; Xiaoxue Liu; Fangfang Yu; Yawei Zhang; Yue Ba; Guoyu Zhou (Environmental Science and Pollution Research, 2022)

Testing the efficacy of camera-trap sampling designs for monitoring giant pandas in a heterogeneous landscape - Zhenxia Cui; Wenai Zhao; Yashuai Zhang; Naxun Zhao; Guoyu Shan; Xiaoping Yu; Xinping Ye (Environmental Science and Pollution Research, 2022)

The effect of urbanization on temperature indices in the Philippines - John A. Manalo; Jun Matsumoto; Hiroshi G. Takahashi; Marcelino Q. Villafuerte; Lyndon Mark P. Olaguera; Guoyu Ren; Thelma A. Cinco (International Journal of Climatology, 2022)
This paper presents a comprehensive analysis of the effect of urbanization on the surface air temperature (SAT) from 1951 to 2018 in the Philippines. The daily minimum temperature ( T min ) and daily maximum temperature ( T max ) records from 34 meteorological stations were used to derive extreme temperature indices. These stations were then classified as urban or rural based on satellite night‐lights. The results showed a significant difference in the SAT trends between urban and rural stations, indicative of the effect of urbanization in the country. Larger and more significant warming trends were observed in indices related to T min than those related to T max . In particular, the effects of urbanization were significant in the annual index series of T min , diurnal temperature range, minimum T min , percentage of days when T min was less than the 10th percentile ( T N10p ), percentage of days when T min was greater than 90th percentile ( T N90p ), and the number of coldest nights. The effects of urbanization were not as clear on the index series of maximum T max ( T Xx ), minimum T max ( T Xn ), percentage of days when T max was less than 10th percentile ( T X10p ), and the number of hottest days. The effects of urbanization on the annual series of extreme temperature indices were statistically significant at the 95% confidence level, with the exception of T max , T Xn , T Xx , T X10p , and the number of hottest days. Further analysis revealed that the effect of urbanization was the greatest during the DJF (December–January–February) season. These findings serve as a baseline study that focuses on the countrywide effect of urbanization on SAT trends in the Philippines.

Pharmacodynamic effects of indobufen compared with aspirin in patients with coronary atherosclerosis - Mingwen Yang; Zekang Ye; Lianlian Mei; Inam Ullah; Chuchu Tan; Guoyu Wang; Qian Gu; Yi Lu; Samee Abdus; Lu Shi; Xiaoxuan Gong; Jianling Bai; et al. (European Journal of Clinical Pharmacology, 2021)

Spatial and temporal variation of dissolved heavy metals in the Lijiang River, China: implication of rainstorm on drinking water quality - Liming Deng; Asfandyar Shahab; He Xiao; Jieyue Li; Saeed Rad; Jinping Jiang; GuoYu; Pingping Jiang; Hongwei Huang; Xiangkui Li; Bilal Ahmad; Jamil Siddique (Environmental Science and Pollution Research, 2021)

Ecological risk assessment of heavy metals in farmland soils in Beijing by three improved risk assessment methods - Rui Chen; Xuying Cai; Guoyu Ding; Fumin Ren; Qi Wang; Nuo Cheng; Jiaxing Liu; Lanxin Li; Rongguang Shi (Environmental Science and Pollution Research, 2021)

Construction of a rAAV-SaCas9 system expressing eGFP and its application to improve muscle mass - Shaoting Weng; Yitian Zhao; Changhong Yu; Xiaofan Wang; Xuehan Xiao; Liqiang Han; Kunpeng Zhang; Jiang Wang; Guoyu Yang (Biotechnology Letters, 2021)
An ideal rAAV gene editing system not only effectively edits genes at specific site, but also prevents the spread of the virus from occurring off-target or carcinogenic risks. This is important for gene editing research at specific site in vivo. We report a single rAAV containing SaCas9 and guide RNAs under the control of subtle EF1a and tRNA promoters. The capacity of rAAV was compressed, and the editing efficiency was similar to that of the classical Cas9 system in vitro and in vivo. And we inserted the sequence of the green fluorescent protein eGFP into rAAV. The number of cells infected with the rAAV and the region in which the rAAV spreads were known by the fluorescent expression of eGFP in cells. In addition, we demonstrated that myostatin gene in the thigh muscles of C57BL/10 mice was knocked out by the rAAV9-SaCas9 system to make muscle mass increased obviously. The protein eGFP into rAAV has significant implications for our indirect analysis of the editing efficiency of SaCas9 in the genome of the target tissue and reduces the harm caused by off-target editing and prevents other tissue mutations. The rAAV system has substantial potential in improving muscle mass and preventing muscle atrophy.

Nitrogen removal processes coupled with nitrification in coastal sediments off the north East China Sea - Yongkai Chang; Guoyu Yin; Lijun Hou; Min Liu; Yanling Zheng; Ping Han; Hongpo Dong; Xia Liang; Dengzhou Gao; Cheng Liu (Journal of Soils and Sediments, 2021)

Historical and recent change in extreme climate over East Asia - Guoyu Ren; Johnny C. L. Chan; Hisayuki Kubota; Zhongshi Zhang; Jinbao Li; Yongxiang Zhang; Yingxian Zhang; Yuda Yang; Yuyu Ren; Xiubao Sun; Yun Su; Yuhui Liu; et al. (Climatic Change, 2021)

Iodine Modifies the Susceptibility of Thyroid to Fluoride Exposure in School-age Children: a Cross-sectional Study in Yellow River Basin, Henan, China - Yuhui Du; Guoyu Zhou; Biao Gong; Jun Ma; Ning An; Minghui Gao; Meng Yang; Qiang Ma; Hui Huang; Qiting Zuo; Yue Ba (Biological Trace Element Research, 2021)

Urbanization reduces frequency of light rain: an example from Beijing City - Ping Yang; Guoyu Ren; Pengcheng Yan; Jingmian Deng (Theoretical and Applied Climatology, 2021)

Roles and Mechanisms of Axon-Guidance Molecules in Alzheimer’s Disease - Lei Zhang; Zhipeng Qi; Jiashuo Li; Minghui Li; Xianchao Du; Shuang Wang; Guoyu Zhou; Bin Xu; Wei Liu; Shuhua Xi; Zhaofa Xu; Yu Deng (Molecular Neurobiology, 2021)

Changes in the diurnal temperature range over East Asia from 1901 to 2018 and its relationship with precipitation - Xiubao Sun; Chunzai Wang; Guoyu Ren (Climatic Change, 2021)

Homogenization and trend analysis of 1960–2015 in situ sea surface temperature observations along the coast of China - Yan Li; Qingyuan Wang; Guoyu Ren; Guosong Wang; Qingliang Zhou (Acta Oceanologica Sinica, 2021)

An imputation method for the climatic data with strong seasonality and spatial correlation - Yun Qin; Guoyu Ren; Panfeng Zhang; Lixiu Wu; Kangmin Wen (Theoretical and Applied Climatology, 2021)

Development of Anisotropy in Sandstone Subjected to Repeated Frost Action - Hailiang Jia; Shun Ding; Fan Zi; Guoyu Li; Yuan Yao (Rock Mechanics and Rock Engineering, 2021)

Response of bacterial communities to mining activity in the alpine area of the Tianshan Mountain region, China - Chengyu Yuan; Fayong Li; Ziqiang Yuan; Guoyu Li; Xinqiang Liang (Environmental Science and Pollution Research, 2021)

Extreme temperature of the mid-eighteenth century as compared to todays in Beijing - Yuyu Ren; Guoyu Ren; Rob Allan; Siqi Zhang (Climatic Change, 2021)

Application of geographically weighted regression model in the estimation of surface air temperature lapse rate - Yun Qin; Guoyu Ren; Yunxin Huang; Panfeng Zhang; Kangmin Wen (Journal of Geographical Sciences, 2021)

Preconception ambient temperature and preterm birth: a time-series study in rural Henan, China - Guoyu Zhou; Meng Yang; Jian Chai; Renjie Sun; Junxi Zhang; Hui Huang; Yawei Zhang; Qihong Deng; Lifang Jiang; Yue Ba (Environmental Science and Pollution Research, 2021)

Surface air pressure–based reconstruction of tropical cyclones affecting Hong Kong since the late nineteenth century - Yingxian Zhang; Yuyu Ren; Guoyu Ren; Yongqiang Zhang (Climatic Change, 2021)

Change in mean and extreme temperature at Yingkou station in Northeast China from 1904 to 2017 - Xiaoying Xue; Guoyu Ren; Xiubao Sun; Panfeng Zhang; Yuyu Ren; Siqi Zhang; Chunyu Zhao; Xiujing Yu (Climatic Change, 2021)
The understanding of centennial trends of extreme temperature has been impeded due to the lack of early-year observations. In this paper, we collect and digitize the daily temperature data set of Northeast China Yingkou meteorological station since 1904. After quality control and homogenization, we analyze the changes of mean and extreme temperature in the past 114 years. The results show that mean temperature (Tmean), maximum temperature (Tmax), and minimum temperature (Tmin) all have increasing trends during 1904–2017. The increase of Tmin is the most obvious with the rate of 0.34 °C/decade. The most significant warming occurs in spring and winter with the rate of Tmean reaching 0.32 °C/decade and 0.31 °C/decade, respectively. Most of the extreme temperature indices as defined using absolute and relative thresholds of Tmax and Tmin also show significant changes, with cold events witnessing a more significant downward trend. The change is similar to that reported for global land and China for the past six decades. It is also found that the extreme highest temperature (1958) and lowest temperature (1920) records all occurred in the first half of the whole period, and the change of extreme temperature indices before 1950 is different from that of the recent decades, in particular for diurnal temperature range (DTR), which shows an opposite trend in the two time periods.

A methodology to determine the optimal quadrat size for desert vegetation surveying based on unmanned aerial vehicle (UAV) RGB photography - Mengyu Hao; Wenli Zhao; Longjun Qin; Peng Mao; Xu Qiu; Lijie Xu; Yu Jiu Xiong; Yili Ran; GuoYu Qiu (International Journal of Remote Sensing, 2021)

Effect of freeze-thaw cycles on the physical and dynamic characteristic of modified Na-bentonite by KCl - Zhongnian Yang; Yuxue Cui; Guoyu Li; Xuesen Liu; Chunxiao Wang; Wei Shi; Xianzhang Ling (Arabian Journal of Geosciences, 2020)

Tempospatial Pattern of Surface Wind Speed and the “Urban Stilling Island” in Beijing City - Ping Yang; Guoyu Ren; Pengcheng Yan; Jingmian Deng (Journal of Meteorological Research, 2020)

N-acyl-homoserine lactones (AHLs) in intertidal marsh: diversity and potential role in nitrogen cycling - Zongxiao Zhang; Yanling Zheng; Ping Han; Hongpo Dong; Xia Liang; Guoyu Yin; Dianming Wu; Yi Yang; Sitong Liu; Min Liu; Lijun Hou (Plant and Soil, 2020)

The correlation between viral clearance and biochemical outcomes of 94 COVID-19 infected discharged patients - Jing Yuan; Rougrong Zou; Lijiao Zeng; Shanglong Kou; Jianfeng Lan; Xiaohe Li; Yanhua Liang; Xiaoyan Ding; Guoyu Tan; Shenghong Tang; Lei Liu; Yingxia Liu; et al. (Inflammation Research, 2020)

Image Dehazing by Incorporating Markov Random Field with Dark Channel Prior - Hao Xu; Yibo Tan; Wenzong Wang; Guoyu Wang (Journal of Ocean University of China, 2020)

Extreme Temperature Change of the Last 110 Years in Changchun, Northeast China - Xiujing Yu; Guoyu Ren; Panfeng Zhang; Jingbiao Hu; Ning Liu; Jianping Li; Chenchen Zhang (Advances in Atmospheric Sciences, 2020)

H2S mediates apoptosis in response to inflammation through PI3K/Akt/NFκB signaling pathway - Yueying Wang; Chengyu Zhang; Chunmei Xu; Luping Feng; Anqi Li; Xiangyang Jin; Shuang Guo; Xianqin Jiao; Jingsong Liu; Yujie Guo; Heshui Zhu; Liqiang Han; et al. (Biotechnology Letters, 2020)

Influence of Pore Water (Ice) Content on the Strength and Deformability of Frozen Argillaceous Siltstone - Hailiang Jia; Fan Zi; Gengshe Yang; Guoyu Li; Yanjun Shen; Qiang Sun; Pengyu Yang (Rock Mechanics and Rock Engineering, 2020)

High‐quality sea surface temperature measurements along coast of the Bohai and Yellow Seas in China and their long‐term trends during 1960–2012 - Yan Li; Lin Mu; Qingyuan Wang; Guoyu Ren; Qinglong You (International Journal of Climatology, 2020)
As semi‐enclosed and shallow seas, the Bohai and Yellow Seas (hereafter, BYS) marine ecosystems are more easily affected by natural and anthropogenic climate changes than those in the open oceans. An accurate assessment of sea surface temperature (SST) change is crucial for the near‐shore water environment. In this work, new high‐quality monthly mean SST time series from 11 in situ coastal hydrological stations at BYS for the period of 1960–2012 have been generated. Monthly mean SST time series were initially subjected to penalized maximal t (PMT) test, using homogeneous monthly mean surface air temperature (SAT) series as references. Homogenized monthly mean SST series were obtained by adjusting all significant change points which have been supported by historic metadata. Our study shows that there are 29 significant change points in these 11 SST series. The majority of them are caused by instrument changes and station relocations—both account for about 51.7 and 31%, respectively. Then, homogeneous SST series are used to assess the long‐term trends. As the regional average, the annual mean homogeneous SST series shows a rapid warming trend, with the rate of 0.21°C/decade. Compared to the homogeneous SST series, the original SST series underestimate the long‐term trend (only 0.13°C/decade), indicating the artificial change points usually result in a warm‐bias in the early period measurements. Seasonally, the most significant warming occurs in boreal winter during the period analysed. The relationships of the significant warming in boreal winter and atmospheric circulation modes have also been investigated. Results reflect the remarkable and direct influence of the East Asian Trough (EAT) on SST along the coastal BYS.

Diurnal and intra-season variation of warm-season temperature in coastal zone of Qinghai Lake - Hongmei Li; Guoyu Ren; Wanzhi Li (Theoretical and Applied Climatology, 2019)

Long-term change in surface air temperature over DPR Korea, 1918–2015 - Kum-Chol Om; Guoyu Ren; Sang-Il Jong; Shuanglin Li; Kang-Chol O; Chol-Ho Ryang; Panfeng Zhang (Theoretical and Applied Climatology, 2019)

Exotic Spartina alterniflora invasion alters soil nitrous oxide emission dynamics in a coastal wetland of China - Dengzhou Gao; Lijun Hou; Xiaofei Li; Min Liu; Yanling Zheng; Guoyu Yin; Yi Yang; Cheng Liu; Ping Han (Plant and Soil, 2019)

Reassessment of urbanization effect on surface air temperature trends at an urban station of North China - Tao Bian; Guoyu Ren (Meteorology and Atmospheric Physics, 2019)

Concurrent droughts and hot extremes in northwest China from 1961 to 2017 - Xin Li; Qinglong You; Guoyu Ren; Suyan Wang; Yuqing Zhang; Jianling Yang; Guangfen Zheng (International Journal of Climatology, 2019)
Northwest China forms the main part of the arid and semiarid areas in China, and even includes some extremely arid areas. This zone of interaction is affected by the westerlies and monsoons making it sensitive to global climate change. Drought is the main type of natural disaster affecting northwest China. Global warming has caused a gradual strengthening of the frequency and intensity of hot extremes, when dry conditions and heatwaves occur simultaneously or successively; as a result, that socioeconomic risks can increase considerably. The present study examined changes in concurrent droughts and hot extremes in northwest China during 1961–2017 based on data from 119 meteorological stations. The result shows that the frequency of concurrent droughts and hot extremes exhibited an increasing trend over most parts of northwest China, while a negative trend occurred in western Xinjiang and at some sites in Qinghai. Concurrent droughts and hot extremes appeared more often in May in western Xinjiang, and in summer in other parts of northwest China. Overall, the trends of such concurrent events, regardless of different definitions, increased from 1961–2017 over northwest China. In particular, from 1981–2017, the trend rose more significantly than in other decades, and reached an abrupt point of change in 1996. Although the trend changed from a positive significant signal to a negative one from 2001–2017, the trend grew 2–3 times from 1997–2017. Changes in large‐scale atmospheric circulation show that an anticyclonic circulation strengthened, increasing in geopotential height over the midhigh latitudes of Eurasia and was centred on Mongolia and Lake Baikal. This enhanced relative humidity in western Xinjiang and eastern Qinghai, and weakened it elsewhere from 1997–2017. These changes have contributed to the changes in the spatial distribution and trends in concurrent droughts and hot extremes in northwest China.

Global diurnal temperature range (DTR) changes since 1901 - Xiubao Sun; Guoyu Ren; Qinglong You; Yuyu Ren; Wenhui Xu; Xiaoying Xue; Yunjian Zhan; Siqi Zhang; Panfeng Zhang (Climate Dynamics, 2019)

Roles of mitochondrial fission inhibition in developmental fluoride neurotoxicity: mechanisms of action in vitro and associations with cognition in rats and children - Qian Zhao; Qiang Niu; Jingwen Chen; Tao Xia; Guoyu Zhou; Pei Li; Lixin Dong; Chunyan Xu; Zhiyuan Tian; Chen Luo; Luming Liu; Shun Zhang; et al. (Archives of Toxicology, 2019)

Relationship Between Fine-Particle Pollution and the Urban Heat Island in Beijing, China: Observational Evidence - Zuofang Zheng; Guoyu Ren; Hong Wang; Junxia Dou; Zhiqiu Gao; Chunfeng Duan; Yubin Li; Jean Paul Ngarukiyimana; Chun Zhao; Chang Cao; Mei Jiang; Yuanjian Yang (Boundary-Layer Meteorology, 2018)

Collating Historic Weather Observations for the East Asian Region: Challenges, Solutions, and Reanalyses - Fiona Williamson; Rob Allan; Guoyu Ren; Tsz-cheung Lee; Wing-hong Lui; Hisayuki Kubota; Jun Matsumoto; Jürg Luterbacher; Clive Wilkinson; Kevin Wood (Advances in Atmospheric Sciences, 2018)

A remarkable climate warming hiatus over Northeast China since 1998 - Xiubao Sun; Guoyu Ren; Yuyu Ren; Yihe Fang; Yulian Liu; Xiaoying Xue; Panfeng Zhang (Theoretical and Applied Climatology, 2018)

The effects of climate change on heating energy consumption of office buildings in different climate zones in China - Fanchao Meng; Mingcai Li; Jingfu Cao; Ji Li; Mingming Xiong; Xiaomei Feng; Guoyu Ren (Theoretical and Applied Climatology, 2018)

Effect of Urbanization on Land-Surface Temperature at an Urban Climate Station in North China - Tao Bian; Guoyu Ren; Yanxia Yue (Boundary-Layer Meteorology, 2017)

Evaluation of gridded precipitation data in the Hindu Kush–Karakoram–Himalaya mountainous area - Shakir Hussain; Xianfang Song; Guoyu Ren; Iqtidar Hussain; Dongmei Han; M.H. Zaman (Hydrological Sciences Journal, 2017)

Identification and expression profiling analysis of TCP family genes involved in growth and development in maize - Wenbo Chai; Pengfei Jiang; Guoyu Huang; Haiyang Jiang; Xiaoyu Li (Physiology and Molecular Biology of Plants, 2017)

Pharmacokinetics of linezolid in plasma and cerebrospinal fluid in patients with cerebral hemorrhage post-surgical intervention - Yan Tang; Lingti Kong; Chenchen Wu; Xiaohua Zhang; Guoyu Lu; Xiaofei Wu (European Journal of Clinical Pharmacology, 2017)

Spatiotemporal characteristics of TOMS-based dust aerosol optical depth in northern China during 1978–2005 - Xiaoyu Ren; Yun Xie; Guoyu Ren (Earth Science Informatics, 2017)

An overview of mainland China temperature change research - Guoyu Ren; Yihui Ding; Guoli Tang (Journal of Meteorological Research, 2017)

Does Fluoride Affect Serum Testosterone and Androgen Binding Protein with Age-Specificity? A Population-Based Cross-Sectional Study in Chinese Male Farmers - Leizhen Duan; Jingyuan Zhu; Keyan Wang; Guoyu Zhou; Yuejin Yang; Liuxin Cui; Hui Huang; Xuemin Cheng; Yue Ba (Biological Trace Element Research, 2016)

A near-Infrared Fluorescent Chemodosimeter for Ratiometric Detecting Fluoride Based on Desilylation Reaction - Puhui Xie; Fengqi Guo; Guangqin Gao; Wei Fan; Guoyu Yang; Lixia Xie (Journal of Fluorescence, 2016)

Correlation analysis of X-band sea clutter in complex domain - Xiaolong Cheng; Tingting Ji; Guoyu Wang; Guangrong Ji (Journal of Ocean University of China, 2016)

A parameter inversion for sea bridge based on high-resolution polarimetric synthetic aperture radar - Genwang Liu; Jie Zhang; Xi Zhang; Junmin Meng; Guoyu Wang (Acta Oceanologica Sinica, 2016)

High level soluble expression and one-step purification of IBDV VP2 protein in Escherichia coli - Dawei Jiang; Yunchao Liu; Aiping Wang; Gaiping Zhang; Guoyu Yang; Yumei Chen; Pengchao Ji; Chang Liu; Yapeng Song; Yunfang Su; Guoqiang Wang; Jucai Wang; et al. (Biotechnology Letters, 2016)

Dual Effects of Humic Acid in Trichloroethylene Removal from Groundwater by Zero-Valent Iron: Hydrophobic Partition and Surface Adsorption - Pinhua Rao; Tongzhou Liu; Xihua Liang; Guoyu Ding (Water, Air, & Soil Pollution, 2016)

Urbanization effects on climatic changes in 24 particular timings of the seasonal cycle in the middle and lower reaches of the Yellow River - Cheng Qian; Guoyu Ren; Yaqing Zhou (Theoretical and Applied Climatology, 2016)

Tempo-spatial characteristics of sub-daily temperature trends in mainland China - Yuyu Ren; David Parker; Guoyu Ren; Robert Dunn (Climate Dynamics, 2016)

Diazoxide protects L6 skeletal myoblasts from H2O2-induced apoptosis via the phosphatidylinositol-3 kinase/Akt pathway - Wei Chen; Yan Liu; Guoyu Xue; Lisi Zhang; Lei Zhang; Suxia Shao (Inflammation Research, 2016)

Survival strategies of Ammopiptanthus mongolicus and Zygophyllum xanthoxylon in saline and drought environments, northwest China - Xiaoxue Shen; Minwei Chai; Jiao Xiang; Ruili Li; Guoyu Qiu (Acta Physiologiae Plantarum, 2015)

Abscisic acid increases leaf starch content of polyethylene glycol-treated wheat seedlings by temporally increasing transcripts of genes encoding starch synthesis enzymes - Liting Wei; Lina Wang; Yang Yang; Guoyu Liu; Yufang Wu; Tiancai Guo; Guozhang Kang (Acta Physiologiae Plantarum, 2015)

A New Turn on Fluorescent Probe for Selective Detection of Cysteine/Homocysteine - Puhui Xie; Guangqin Gao; Juanjuan Liu; Qiu Jin; Guoyu Yang (Journal of Fluorescence, 2015)

Efficacy of entomopathogenic Steinernema and Heterorhabditis nematodes against Holotrichia oblita - Wenxiu Guo; Xun Yan; Guoyu Zhao; Jinghua Chen; Richou Han (Journal of Pest Science, 2015)

Laboratory testing on heat transfer of frozen soil blocks used as backfills of pile foundation in permafrost along Qinghai-Tibet electrical transmission line - Guoyu Li; Qihao Yu; Wei Ma; Yanhu Mu; Xingbai Li; Zhaoyu Chen (Arabian Journal of Geosciences, 2015)

The relative contribution of climate and cultivar renewal to shaping rice yields in China since 1981 - Yanling Song; Chunyi Wang; Guoyu Ren; Yanxia Zhao; Hans W. Linderholm (Theoretical and Applied Climatology, 2015)

An approach to underwater image enhancement based on image structural decomposition - Tingting Ji; Guoyu Wang (Journal of Ocean University of China, 2015)

A Dansyl-Rhodamine Ratiometric Fluorescent Probe for Hg2+ Based on FRET Mechanism - Puhui Xie; Fengqi Guo; Lingyu Wang; Sen Yang; Denghui Yao; Guoyu Yang (Journal of Fluorescence, 2015)

Urbanization effect on long-term trends of extreme temperature indices at Shijiazhuang station, North China - Tao Bian; Guoyu Ren; Bingxiang Zhang; Lei Zhang; Yanxia Yue (Theoretical and Applied Climatology, 2015)

Denitrification and Anaerobic Ammonium Oxidization Across the Sediment–Water Interface in the Hypereutrophic Ecosystem, Jinpu Bay, in the Northeastern Coast of China - Guoyu Yin; Lijun Hou; Haibo Zong; Pingxing Ding; Min Liu; Shufang Zhang; Xunliang Cheng; Junliang Zhou (Estuaries and Coasts, 2015)

Present and projected degree days in China from observation, reanalysis and simulations - Qinglong You; Klaus Fraedrich; Frank Sielmann; Jinzhong Min; Shichang Kang; Zhenming Ji; Xiuhua Zhu; Guoyu Ren (Climate Dynamics, 2014)

Threat of heavy metal contamination in eight mangrove plants from the Futian mangrove forest, China - Bei He; Ruili Li; Minwei Chai; Guoyu Qiu (Environmental Geochemistry and Health, 2014)

A Novel Ratiometric Fluorescent Mercury Probe Based on Deprotonation-ICT Mechanism - Puhui Xie; Fengqi Guo; Sen Yang; Denghui Yao; Guoyu Yang; Lixia Xie (Journal of Fluorescence, 2014)

Growth and physiological responses to copper stress in a halophyte Spartina alterniflora (Poaceae) - Minwei Chai; Fuchen Shi; Ruili Li; Guoyu Qiu; Fuchun Liu; Limin Liu (Acta Physiologiae Plantarum, 2014)

Variability of temperature in the Tibetan Plateau based on homogenized surface stations and reanalysis data - Qinglong You; Klaus Fraedrich; Guoyu Ren; Nick Pepin; Shichang Kang (International Journal of Climatology, 2013)
The Tibetan Plateau (TP) with an average elevation of over 4000 m a.s.l. is the world's highest and most extensive highland. The scarcity of climatic observations limits our understanding of surface air temperature change in the region. Thus, we compare temperatures and their trends from 71 homogenized surface stations (with elevations above 2000 m a.s.l.) with National Centers for Environmental Prediction/National Center for Atmospheric Research (NCEP/NCAR) Reanalysis (NCEP/NCAR hereafter) and European Centre for Medium‐Range Weather Forecasts (ECMWF) reanalysis (ERA‐40 hereafter) in the eastern and central TP during 1961–2004. For current climatology, ERA‐40 is more similar to the surface stations than NCEP/NCAR. Compared with surface stations, both NCEP/NCAR and ERA‐40 reanalyses have cold biases, which are mainly a result of differences in topographical height, and station aspect and slope. Warming trends at the surface stations are on average stronger than in both reanalyses, but ERA‐40 captures the surface warming more clearly than NCEP/NCAR on an annual and seasonal basis. Since ERA‐40 more closely represents the surface temperatures and their trends in the central and eastern TP, ERA‐40 predictions are selected to examine change in the western TP where there are few surface stations. NCEP/NCAR, on the other hand, is more representative of free air temperature conditions. The ‘observation minus reanalysis’ (OMR) method can be used to estimate the impact of surface changes on climate by computing the difference between surface observations and NCEP/NCAR (which only contains the forcing influencing the assimilated atmospheric trends). The OMR trend is significantly increasing but the extent to which the changes in local environment are responsible needs further study. Copyright © 2012 Royal Meteorological Society

Winter temperature extremes in China and their possible causes - Qinglong You; Guoyu Ren; Klaus Fraedrich; Shichang Kang; Yuyu Ren; Pengling Wang (International Journal of Climatology, 2013)
Cold and warm temperature extremes predominantly occurring in winter gained much more attention than mean temperatures. On the basis of daily maximum and minimum surface air temperature records at 303 meteorological stations in China, the spatial and temporal distributions of five indices for winter (DJF: December, subsequent January and February) temperature extremes are analysed during 1961–2003. For the majority of stations, the frequency of cold days/nights decreases by − 1.33/− 2.98 and warm days/nights increases by 0.92/2.35 d/decade, respectively. Cold days/nights are significantly negatively correlated with the Arctic Oscillation (AO) index, while warm days/nights are positively correlated with the AO. The diurnal temperature range (DTR) has a declining trend with rate of − 0.25 °C/decade and positive correlation with the AO index. Compared with other regions in China, stations in the northern China have larger trend magnitudes and stronger correlations with the AO index, and the AO can explain more than 50% of winter temperature extreme change in China. Compared with the annual basis, the winter temperature extremes have larger trend magnitudes, which reflect the rapid warming. During strongly positive AO index years, enhanced contrast tropospheric temperature (defined as the average of air temperature vertically integrated between 200 hPa and 1000 hPa based on the National Centers for Environmental Prediction/National Center for Atmospheric Research reanalysis) between the north of China and the southern China weakens the East Asian winter monsoon which in turn reduces cold outbreaks in the northern and eastern China. The composites of large‐scale atmospheric circulation are consistent with the asymmetrical changes of the geopotential height, zonal and meridional winds at high and mid latitudes at troposphere. Meanwhile, the linkage between the AO and solar activity also modulates the winter temperature extremes, while the mechanism needs to be investigated. Copyright © 2012 Royal Meteorological Society

Erratum to: Decadal variation of surface solar radiation in the Tibetan Plateau from observations, reanalysis and model simulations - Qinglong You; Arturo Sanchez-Lorenzo; Martin Wild; Doris Folini; Klaus Fraedrich; Guoyu Ren; Shichang Kang (Climate Dynamics, 2013)

Decadal variation of surface solar radiation in the Tibetan Plateau from observations, reanalysis and model simulations - Qinglong You; Arturo Sanchez-Lorenzo; Martin Wild; Doris Folini; Klaus Fraedrich; Guoyu Ren; Shichang Kang (Climate Dynamics, 2013)

Recent progress in studies of climate change in China - Guoyu Ren; Yihui Ding; Zongci Zhao; Jingyun Zheng; Tongwen Wu; Guoli Tang; Ying Xu (Advances in Atmospheric Sciences, 2012)

Inconsistencies of precipitation in the eastern and central Tibetan Plateau between surface adjusted data and reanalysis - Qinglong You; Klaus Fraedrich; Guoyu Ren; Baisheng Ye; Xianhong Meng; Shichang Kang (Theoretical and Applied Climatology, 2012)

QTL detection of seven spike-related traits and their genetic correlations in wheat using two related RIL populations - Fa Cui; Anming Ding; Jun Li; Chunhua Zhao; Lin Wang; Xiuqin Wang; Xiaolei Qi; Xingfeng Li; Guoyu Li; Jurong Gao; Honggang Wang (Euphytica, 2012)

CTLA-4 exon 1 +49 polymorphism alone and in a haplotype with −318 promoter polymorphism may confer susceptibility to chronic HBV infection in Chinese Han patients - Shaoqiong Duan; Guoyu Zhang; Qunying Han; Zhu Li; Zhengwen Liu; Jinghong Chen; Yi Lv; Na Li; Yawen Wang; Man Li; Sai Lou; Mingbo Yang; et al. (Molecular Biology Reports, 2011)

Associations between cytotoxic T lymphocyte-associated antigen-4 polymorphisms and serum tumor necrosis factor-α and interferon-γ levels in patients with chronic hepatitis B virus infection - Qunying Han; Shaoqiong Duan; Guoyu Zhang; Zhu Li; Na Li; Qianqian Zhu; Yi Lv; Jinghong Chen; Zhengwen Liu (Inflammation Research, 2011)

Soluble vascular endothelial growth factor (VEGF) receptor-1 inhibits migration of human monocytic THP-1 cells in response to VEGF - Cansheng Zhu; Zhaojun Xiong; Xiaohong Chen; Zhengqi Lu; Guoyu Zhou; Dunjing Wang; Jian Bao; Xueqiang Hu (Inflammation Research, 2011)

Characteristics of the lower layer of sandstorms in the Minqin desert-oasis zone - Ming Zhao; KeJie Zhan; ZiHui Yang; ErTian Fang; GuoYu Qiu; QiangQiang Wang; YinChang Zhang; ShuJiang Guo; AiDe Li; JingChun Zhang (Science China Earth Sciences, 2011)

Elevated sICAM-1 levels in patients with hemorrhagic fever with renal syndrome caused by Hantaan virus - Qunying Han; Lei Zhang; Zhengwen Liu; Wen Kang; Sai Lou; Jianming Qiu; Zhu Li; Guoyu Zhang; Yawen Wang; Man Li; Na Li (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Changes in means and extreme events of temperature and precipitation in the Asia‐Pacific Network region, 1955–2007 - Gwangyong Choi; Dean Collins; Guoyu Ren; Blair Trewin; Marina Baldi; Yoshikazu Fukuda; Muhammad Afzaal; Theeraluk Pianmana; Purevjav Gomboluudev; Pham Thi Thanh Huong; Norlisam Lias; Won‐Tae Kwon; et al. (International Journal of Climatology, 2009)
In this study, spatial and temporal patterns of changes in extreme events of temperature and precipitation at 143 weather stations in ten Asia‐Pacific Network (APN) countries and their associations with changes in climate means are examined for the 1955–2007 period. Averaged over the APN region, annual frequency of cool nights (days) has decreased by 6.4 days/decade (3.3 days/decade), whereas the frequency of warm nights (days) has increased by 5.4 days/decade (3.9 days/decade). The change rates in the annual frequency of warm nights (days) over the last 20 years (1988–2007) have exceeded those over the full 1955–2007 period by a factor of 1.8 (3.4). Seasonally, the frequencies of summer warm nights and days are changing more rapidly per unit change in mean temperatures than the corresponding frequencies for cool nights and days. However, normalization of the extreme and mean series shows that the rate of changes in extreme temperature events are generally less than that of mean temperatures, except for winter cold nights which are changing as rapidly as the winter mean minimum temperature. These results indicate that there have been seasonally and diurnally asymmetric changes in extreme temperature events relative to recent increases in temperature means in the APN region. There are no systematic, regional trends over the study period in total precipitation, or in the frequency and duration of extreme precipitation events. Statistically significant trends in extreme precipitation events are observed at fewer than 30% of all weather stations, with no spatially coherent pattern of change, whereas statistically significant changes in extreme temperature events have occurred at more than 70% of all weather stations, forming strongly coherent spatial patterns. Copyright © 2009 Royal Meteorological Society

Comparison of two split-window methods for retrieving land surface temperature from MODIS data - Shaohua Zhao; Qiming Qin; Yonghui Yang; Yujiu Xiong; Guoyu Qiu (Journal of Earth System Science, 2009)

Global analysis of gene expression in flower buds of Ms-cd1 Brassica oleracea conferring male sterility by using an Arabidopsis microarray - Jungen Kang; Guoyu Zhang; Guusje Bonnema; Zhiyuan Fang; Xiaowu Wang (Plant Molecular Biology, 2008)

Detection, causes and projection of climate change over China: An overview of recent progress - Yihui Ding; Guoyu Ren; Zongci Zhao; Ying Xu; Yong Luo; Qiaoping Li; Jin Zhang (Advances in Atmospheric Sciences, 2007)

Changes in forest cover in China during the Holocene - Guoyu Ren (Vegetation History and Archaeobotany, 2006)

Spatial and temporal variations and controlling factors of potential evapotranspiration in China: 1956–2000 - Ge Gao; Deliang Chen; Guoyu Ren; Yu Chen; Yaoming Liao (Journal of Geographical Sciences, 2006)

Decline of the mid‐ to late Holocene forests in China: climatic change or human impact? - Guoyu Ren (Journal of Quaternary Science, 2000)

Decline of the mid- to late Holocene forests in China: climatic change or human impact? - Guoyu Ren (Journal of Quaternary Science, 2000)

The mapping of Holocene pollen data in China - Guoyu Ren; Hans-Jürgen Beug (Vegetation History and Archaeobotany, 1999)